Postharvest control of Botryosphaeria dothidea-induced pear ring rot by Chrysanthemum indicum essential oil: Composition, efficacy, and mechanistic insights - Bin Wang; Sha-Sha Liu; Jia-Ying Wu; Meng-Ran Yu; Yun-Kai Lv; Jian Wang; Li-Juan Wang; Fei Cao (Postharvest Biology and Technology, 2026)

Potato residue chips as corn replacement in Angus bulls: Effects on carcass characteristics, meat quality, and serum metabolites - Chang-Xiao Shi; Hui-Li Wang; Ying-Qi Li; Muhammad Aziz-ur-Rahman; Si-Yu Zhang; Jia-Jie Deng; Wen-Xi Zhao; Xing-Yue Yi; Yi-Min Zhang; Yang He; Bing-hai Cao; Hua-Wei Su (Food and Humanity, 2026)

Relative importance of park features and within-park configuration in shaping butterfly diversity in Beijing - Zixiang Xiao; Weiqi Zhou; Zhimin Su; Li Zhang; Ying Cao; Yu Cao; Zhiheng Chen; Mengwei Peng; Xu Sun; Zhong Zheng (Urban Forestry & Urban Greening, 2026)

MAFF mediates transcriptional activation of CFLAR to reduce regulatory T cell apoptosis and inhibit diabetic retinopathy progression - Xinle Kang; Jian Li; Ying Cao (Tissue and Cell, 2026)

Engineering compartmentalized utilization of acetate with glucose for high-level squalene and C30 carotenoids production in Yarrowia lipolytica - Kun Zhu; Chengjiao Cao; Yonghao Li; Huifen Liang; Xiangyu Zhu; Shuli Liang; Ying Lin (Chemical Engineering Journal, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Progressive fluorescence amplification of molecular rotors via G-run-length engineering of G-rich DNA scaffolds - Ruo-Yao Cui; Yu-Chao Cao; Yi-Xuan Gu; Ling-Li Zhao; Xu-Yang Shen; Ying Liu; Ying-Lin Zhou; Xin-Xiang Zhang (Analytica Chimica Acta, 2026)

Investigating the impact of urban morphology and building change trajectories on annual temperature cycle - Ling Li; Shisong Cao; Mingyi Du; Ying Liang; Jingyi Chen; Rui Liu; Nuan Wang (Sustainable Cities and Society, 2026)

Complexation mechanism of pectins with varying esterification degrees and pea protein isolate: Effects on protein solubility, emulsifying properties, and emulsion stability - Ying Kuang; Tao Wang; Jiapeng Wu; Huiyu Liu; Yichen Yang; Kai Chen; Bo Peng; Yi Liu; Qian Zhang; Fatang Jiang; Kao Wu; Jia Liu; et al. (Journal of Food Engineering, 2026)

Chromium detoxification in hydroponic systems: Leveraging fungal and bacterial synergies for enhanced bioremediation - Frank Sesu; Obey Kudakwashe Zveushe; Yukun Wu; Shirou Cao; Edidiong Okokon Atakpa; Kwame Eduam Baiden Frempong; Osei Duah Matthew; Jin Li; Zhou Haichao; Faqin Dong; Han Ying (Journal of Environmental Chemical Engineering, 2026)

Enzymatic double crosslinking strategy: remodeling of pea protein isolate hydrogels through transglutaminase and gelatin modification to redesign their functional properties - Mengke Li; Mengle Li; Ying Qian; Xiangsong Chen; Jianglin Chen; Long Jin; Lili Cao; Min Pang (Food Research International, 2026)

GABA-enriched Lactobacillus buchneri XBMU-C1 fermentation broth lowers blood pressure in L-NAME-induced hypertensive rats via RAAS suppression and PI3K/Akt/eNOS activation - Dandan Gao; Chenchen Wang; Ying Chen; Jiwen Wang; Junyao Mei; Yujie Cao; Xuankang Yang; Shangyun Kang; Jinyong Ma; Ping Li (Food Research International, 2026)

Effects of long-term room temperature storage on phenolic acids and furfurals in honey - Fanhua Wu; Xinyu Wang; Jinkui Wu; Dianli Yang; Chu Li; Ying Zhang; Ni Cheng; Haoan Zhao; Wei Cao (Food Chemistry, 2026)

Alcohol and high-fat diet aggravate colitis-induced liver injury via glucocorticoid/IL-6-SAA1 axis in mice - Mingrui Zhao; Han Li; Xinghua Gao; Huijuan Da; Xun Cui; Dongquan Jing; Qixiang Zhao; Ying Wang; Yanling Guo; Zhenhua Gao; Shentian Zhuang; Qiuhua Cao (Food and Chemical Toxicology, 2026)

W-doped Na3V2(PO4)2F3/C cathode materials for high-rate and long-life sodium-ion batteries - Ying Liu; Ruifang Jiao; Yu Cao; Yang Shao; Chenping Li; Rundong Wan; Ruian Huang; Zhengfu Zhang; Yuejing Bin; Jinsong Wang; Xiaoping Yang (Chemical Engineering Journal, 2026)

A heterojunction nanozyme with dual enzyme-like activities for synergistic cascade catalysis and photothermal tumor therapy - Qianqian Qiao; Fei Hu; Zerui Liu; Tao Liao; Baosheng Guo; Ying Kuang; Cao Li (Chemical Engineering Journal, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Resilience dynamics across sea-land gradients in port cities and river deltas - Jie Zhong; Yongchao Liu; Chao Ying; Luodan Cao; Ruiqing Liu; Chi Zhou; Jialin Li (Ocean & Coastal Management, 2026)

Pseudomonas chlororaphis YL21 synergistically controls Fusarium crown rot of wheat by reshaping rhizosphere microbiota and reprogramming host defense metabolism - Ying Gao; Jianghua Chen; Yunxiang Zhang; Jie Duan; Tian Qiu; Jianing Wu; Xintong Wang; Jin Li; Wei Cao; Haifeng Gao (Pesticide Biochemistry and Physiology, 2026)

Structurally diverse diterpenoids from Euphorbia milii: Discovery and RORγt-binding evaluation - Meng-Yuan Dai; Xue-Li Hu; Wen-Chang Li; Zhi Lu; Bin-Yuan Jiang; Hua-Mei Chen; Ying Zeng; Dong-Hua Cao (Phytochemistry, 2026)

Copper induces depressive-like behavior through neuronal lipid accumulation mediated by Lipin-1 - Qingqi Li; Xueer Cao; Hongrong Wu; Ying Xu; Zhaolin Duan; Jianfeng Zhao (NeuroToxicology, 2026)

Genomic analysis of an Arctic marine Tenacibaculum sp. SM2510 reveals its genetic potential for glutathione utilization - Can You; Han Wang; Jing-Li Lv; Chang Tan; Xi-Ying Zhang; Hai-Yan Cao (Marine Genomics, 2026)

Integrated bioremediation of microplastics-cadmium co-contamination via chitosan-sugarcane residue encapsulated fungal consortia - Iqra Arshad; Jin Li; Sumbal Sajid; Farhan Nabi; Shirou Cao; Yukun Wu; Xingxu Chen; Meghwar Madan Lal; Edidiong Okokon Atakpa; Ying Han (Journal of Hazardous Materials, 2026)

Internal transport performance of large-area proton exchange membrane fuel cell based on the gas distribution zone of “bifurcated-type” configuration and under the impact of coolant - Ying Li; Huqiang Jiang; Yaqing Li; Haoyan Fang; Jing Cao; Qingshan Liu; Yong Zhang (Fuel, 2026)

Atrazine-modified root exudates reshape the rhizobium community and regulate soybean growth - Duo Jiang; Zhao Jiang; Wei Li; Ke Du; Yi Wu; Zhengze Du; Yining Gui; Bo Cao; Yuexuan Ma; Ying Zhang (Applied Soil Ecology, 2026)

Dual-space co-evolution with temporal information learning for multi-modal multi-objective optimization - Xiaojian Cao; Ying Huang; Zhou Yang; Wei Li (Swarm and Evolutionary Computation, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Nationwide dynamic monitoring and hazardous emission quantification of crop residue burning in China: A Fengyun satellite-integrated active-fire fusion approach - Jia Li; Ying Zhou; Jianlei Lang; Xiaoyang Zhang; Chao Liu; Dongsheng Chen; Xiangchen Xia; Xingduo Li; Jing Liu; Jing Cao; Wanting Zhang; Shuiyuan Cheng (Journal of Hazardous Materials, 2026)

Identification and molecular mechanism study of novel pancreatic lipase and cholesteryl esterase inhibitory peptides from yak whey protein hydrolysates - Zhehong Jia; Hongjuan Li; Yingrui Lu; Chengrui Shi; Ying Wang; Xuhui Chen; Weibing Zhang; Deyuan Lu; Yongqiang Cao; Pengjie Wang; Pengcheng Wen (Food Chemistry, 2026)

Machine learning for uranium separation prediction in smart capacitive deionization: A feasibility review - Zhurui Shao; Xiaoyan Wu; Manlu Cao; Xiaoyun Li; Zhaowen Cheng; Qiong Tian; Dun Wei; Xiaowen Zhang; Yilong Hua; Qi Fang; Ying Peng; Chengzhi Geng; et al. (Desalination, 2026)

Electronic communication between platinum single atom and metal-organic framework enable efficient photo-assisted hydrogen production - Xu Li; Yu Zhang; Dantong Zhang; Qunzhi Ma; Jun Zhang; Jiayi Li; Wei Liu; Xiaojie Ma; Ying Wang; Wenyu Wang; Liyun Cao; Jianfeng Huang; et al. (Chemical Engineering Journal, 2026)

Understanding the microscopic tribo-piezo-flexoelectric coupling mechanism at ferroelectric polymer-metal interfaces from molecular and electronic structure - Wensong Diao; Xiaoli Wang; Lizhou Li; Genshuo Liu; Wei Shi; Ying Cao (Chemical Engineering Journal, 2026)

RDO3 REPRESSOR 27, a new MED25 allele, regulates seed dormancy dependent on DOG1 and ABA pathways in Arabidopsis - Yue Yang; Xiao-Ying Li; Run Ding; Hong Cao; Yongxiu Liu; Yu Li (Planta, 2026)

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

Numerical Investigation of Natural Gas Pipeline Physical Explosions with a Compressibility-Factor-Based Non-Ideal Initial State Correction - Wenwen Li; Yuguang Cao; Ying Zhen; Qiqi Deng; Hongtu Lu; Zikang Liu (Process Safety and Environmental Protection, 2026)

Tuning electron transfer and surface dual-sites for synergistic peroxymonosulfate activation toward efficient 2,4,6‑trichlorophenol degradation - Jingyi Wang; Yitong Liu; Wenhui Qiu; Lin Zhang; Kaige Li; Ran Wang; Bo Cao; Jianhua Qu; Ying Zhang (Process Safety and Environmental Protection, 2026)

From rapid reduction to stable immobilization: A regenerative 4D FeMgAl layered double hydroxide–microbial strategy for chromium remediation - Edidiong Okokon Atakpa; Shirou Cao; Wu Yukun; Liberty Chidewe; Kwame Frempong Eduam Baiden; Jin Li; Xingxu Chen; Fidèle Suanon; Iqra Arshad; Lei Zhou; Lv Zhenzhen; Huo Tingting; et al. (Journal of Hazardous Materials, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

Targeting SYK to alleviate MDSC-driven immunosuppression and augment anti-PD1 efficacy - Zhiyang Zeng; Xiya Cao; Changwei Li; Youyuan He; Haozhe Guo; Xiaoya Cao; Tingyue Gong; Jialiang Sun; Yaqiang Hu; Zhongwei Hu; Yuxuan Lai; Dan Zhang; et al. (Science China Life Sciences, 2026)

Corrigendum to “Development and evaluation of a nanozyme-based lateral flow assay strip for avian leukosis virus detection” [The Veterinary Journal 315 (2026) 106508] - Liyan Cao; Kexiong Wang; Jie Wang; Xiaoying Jin; Bin Li; Xiaomei Wang; Ying Shen; Rui Zeng; Kai Li (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Multi-omics dissection of a ceRNA–PKS regulatory network underlying lead tolerance in Morchella sextelata - Shishi Liu; Zonglin Deng; Xuelian Cao; Chang Tian; Lixu Liu; Yun Ju; Yiping Li; Jie Tang; Liyuan Xie; Ying Chen (Journal of Hazardous Materials, 2026)

A Janus-structured photothermal evaporator with black phosphorus for efficient and salt-resistant solar desalination - Mengnan Qu; Jin Zhang; Jiehui Li; Yuhang Gao; Ying Zhang; Mengge Cao; Zaiwen Yang; Lin Liu; Chao Wang; Jinmei He (Journal of Environmental Chemical Engineering, 2026)

Sustainable conversion of natural gas to high-value chemicals - Jie Qiu; Yuehan Cao; Changmin Tuo; Sibo Wang; Yong He; Xingran Zhao; Zhiyong Zou; Wang Yu; Yi Li; Heng Zheng; Dajun Wang; Zeai Huang; et al. (Gas Science and Engineering, 2026)

Nutrient degradation by fungal pathogens in bamboo: Mechanisms and implications for the conservation of giant pandas - Kashf Wajid; Wenhao Wang; Kexin Wu; Muqadus Zafar; Hao Jiang; Boya Wang; Yongping Li; Qilin Dai; Xin Zhao; Dengguo Tang; Dongling Zhang; Ying Cao; et al. (Fungal Biology Reviews, 2026)

pH-driven dual sensing: A single fluorescent probe for real-time food spoilage tracking and microfluidic sorting of acid-producing bacteria - Wentong Qi; Huawei Niu; Lina Zhao; Xuan Li; Li Cao; Ying Wu; Shaobin Gu (Food Chemistry, 2026)

Atomic condensation of Na and K vapor followed by oxidation in lunar impact glass beads revealed by Chang’E-6 - Ming-Yang Li; Ying-Kui Xu; Dan Zhu; De-Liang Wang; Yi-Cao Zhou; Bing Mo; Shi-Jie Li; Yang Li; Xiong-Yao Li; Jian-Zhong Liu; Wei Du; Yun Liu (Earth and Planetary Science Letters, 2026)

Tetrahedral-site doping modulation in Mn3O4 toward improved water oxidation activity and stability - Shaokai Ma; Zihang Cao; Yiran Zhao; Zihao Wang; Ying Li; Xuewen Xu; Yuanhui Ma; Yanming Xue; Chengchun Tang; Jun Zhang (Chemical Engineering Journal, 2026)

Spatially‐Uneven Observations Cause Overestimation of Global Soil Respiration - Li Cao; Tao Zhou; Jingyu Zeng; Yajie Zhang; Yancheng Qu; Jian Liu; Qi Zhang; Jingzhou Zhang; Peixia Liu; Wenjuan Zhang; Ying Yu (Global Change Biology, 2026)
Spatial unevenness in observation sites may hinder accurate global soil respiration (R S ) quantification. We quantified site representativeness using Voronoi volumes within an environmental feature space and implemented an iterative pruning strategy to identify a representative‐optimal subset (1363 sites). Using process‐based models as benchmarks, we developed a Representative‐optimal Model (RM) to simulate global R S dynamics (1982–2022). Compared to the Full‐set model (FM), the RM significantly enhanced spatial consistency with benchmarks and improved alignment with FLUXNET observations and atmospheric CO 2 fluctuations. Neglecting representativeness led to a 6.4 PgC year −1 overestimation of global R S (94.1 vs. 100.5 PgC year −1 ), while simultaneously underestimating its long‐term trend and interannual variability. Arid zones contributed > 50% of this downward revision, reflecting corrected biases in water‐limited regions. These findings demonstrate that optimizing existing dataset representativeness can effectively mitigate systematic biases and refine global carbon budget accounting. While expanding observational networks remains a long‐term priority, we advocate routinely integrating spatial representativeness optimization into data‐driven workflows to immediately correct structural sampling biases.

The TCP transcription factor RmTCP5 shapes leaf development by modulating auxin and cytokinin homeostasis in Rosa multiflora - Wan Zhu; Ying Bao; Huijia Cao; Yuzhen Li; Manzhu Bao; Ting Peng; Wei Zhang (Journal of Plant Physiology, 2026)

A transformer-reinforcement learning framework integrating acoustic thermometry for multi-pollutant prediction and control in a full-scale WtE plant in China - Yuxuan Ying; Linyi Chen; Hanqing Yang; Tianyi Zhu; Weiwei Cao; Zhenwei Yang; Hongyu Sun; Jinghao Ye; Yu Liu; Yunhua Zhao; Weiya Jin; Mi Yan; et al. (Journal of Cleaner Production, 2026)

Non-targeted metabolomics coupled with simulated processing strategy reveals temperature-driven flavonoid and organic acid transformations in Typhae pollen - Fang Tian; Mingqi Chen; Ying Zhang; Hui Cao; Menghua Wu; Jinju Zhang; Hanpeng Jiang; Wen Li; Zhiguo Ma (Food Research International, 2026)

Mitigating rainfall induced erosion of rammed earth in Great Wall by protective coating: Insights from laboratory study - Jiefeng Liu; Haiying Cao; Zhen Li; Jianshe Zhao; Liang Liu; Ying Guo (Engineering Geology, 2026)

A novel strategy of bulk-surface Al/Ti continuous modification for improving structural stability and electrochemical performance of ultra-high-nickel cathode materials - Huali Zhu; Jialong Ying; Yiying Wang; Ziyi Huang; Sunjing Yan; Yi Zhong; Qiulin He; Penghui Cao; Chuanchang Li; Zhaoyong Chen (Chemical Engineering Journal, 2026)

The distinct circulation configuration modulating the interannual variability of summer compound hot and dry events over the Yangtze River Valley - Jianqian Li; Chao Wang; Ying Liu; Liguang Wu; Haikun Zhao; Jian Cao (Climate Dynamics, 2026)

Ternary network derived from polyphenol-inspired sticky nanoparticle: nanofiltration separation efficiency and end-of-life membrane regeneration potential - Jiaying Yan; Panpan Wang; Ying Cao; Jinlong Zhu; Xingyan Jin; Luwei Li; Chuandong Wu; Hao Zhang; Hui Xie; Jun Ma (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Poly(deep eutectic solvent)@MOF-801 for technical surveillance of carbaryl: Pesticide residue safety control strategy - Xicheng He; Yumin Yang; Ying Cao; Ziming Wang; Haixiang Li; Zhiliu Liu; Yan Wang; Fengyun Li; Qian Zhang; Abdulla Yusuf; Feiran Li; Mi Hu; et al. (Journal of Environmental Management, 2026)

Short- and medium-chained chlorinated paraffins in soils and sediments in China: Spatiotemporal distributions, ecological risks, and driving mechanisms - Qiang Li; Ying Cao; Liansheng He; Cunfu Gao; Tian Meng; Yafeng Liu; Xiaoxue Liu (Journal of Environmental Sciences, 2026)

Relationship between sulfur compounds and Baijiu flavor: composition, flavor characteristics, and modulation - Ting Li; Ying Lang; Yangyang Huo; Xuanjing Ren; Tianyi Cao; Yao Long; Botian Wu; Mingquan Huang; Baoguo Sun; Jihong Wu; Hehe Li (Food Chemistry, 2026)

Oxidative profile and degradation patterns of plasma-activated water-treated golden pompano (Trachinotus ovatus) during chilled storage: Insights based on data independent acquisition (DIA) quantitative proteomics - Xin Zhang; Boyan Zhao; Ying Liang; Andi Febrisiantosa; Qian Li; Bin Zhang; Soojin Jun; Yanfu He; Longteng Zhang; Jun Cao; Chuan Li (Food Chemistry, 2026)

Synergistic regulation of pore structure and surface charge in COF-based membranes for monovalent ion sieving - Long Li; Qian Cao; Renzhong Wang; Ying Li; Yang Zhao; Yiqun Fan; Zhaohua Li; Feng Shao (Desalination, 2026)

City-scale assessment of green-roof carbon: high-frequency chamber fluxes and district inventories reveal microclimate-driven sinks and seasonal resilience - Feilong Shen; Zhenzhu Cao; Chongyang Zhang; Ying Zhao; Hui Li; Shiliang Liu; Guiying Jiang; Jiawei Yang; Fang Liu (Building and Environment, 2026)

Bellidifolin mitigates doxorubicin-induced myocardial injury via regulating oxidative stress, inflammation, and apoptosis: a combination of network pharmacology and experiments - Ying Cao; Yutao Jia; Rongrong Chen; Cheng Dai; Hongyao Ge; Shenhan Duan; Aiying Li; Jiangli Wu (Journal of Molecular Histology, 2026)

Applicability assessment of molecular tools and identification of lines suitable for genetic transformation in the red alga Pyropia yezoensis - Xuexue Cao; Jiaxin Qu; Jia hui Sun; Yichi Li; Ying Sun; Yunxiang Mao; Fanna Kong (Algae, 2026)
Pyropia yezoensis, a red macroalga distributed in the intertidal zone, serves as an important model organism for studying the adaptive mechanisms of intertidal seaweeds in response to abiotic stressors. Additionally, it is a significant economic seaweed due to its high nutrient content and is widely cultivated in China, Japan, and Korea. Despite its importance, existing molecular tools for genetic transformation remain limited and require further development to enhance our understanding of P. yezoensis biology. To address this limitation, based on previous studies, we firstly evaluated the expression of eight fluorescent proteins (FPs) in P. yezoensis. Our findings confirmed that PyZsYellow, PyZsGFP, and PysGFP can be detected successfully their specific fluorescent signals within the cells of P. yezoensis thalli. Notably, PyZsGFP demonstrated effectiveness in sporophytic filaments. 2×SV40 and PyNP may function as nuclear localization signal sequences, effectively directing the FP to localize within the nucleus of cells in P. yezoensis. T2A linker can mediate protein cleavage, to express the multiple genes in one construct, enabling them to function independently in P. yezoensis. Furthermore, we identified that the RZ line exhibited the highest transformation potential, while the middle region of thalli showed the superior transformation efficiency. A significant correlation between cell size and transformation efficiency. These findings will contribute to developing a systematic toolkit for conducting genetic transformations and elucidating gene functions in P. yezoensis.

Spatial-adaptive active learning identifies ultra-durable and highly active catalysts for acidic oxygen evolution reaction - Bin Cao; Yin Qin; Yan Luo; Zhehan Ying; Zilin Yan; Lu-Tao Weng; Kaikai Li; Tong-Yi Zhang (Science Bulletin, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

Tracking marine phycotoxins: spatial distribution and source elucidation of domoic acid and lipophilic shellfish toxins in the Beibu Gulf, South China Sea - Ying Ji; Guowang Yan; Guixiang Wang; Yadong Cao; Jiangbing Qiu; Tianshen Li; Xin Luo; Wenlu Lan; Zhaohui Wang; Aifeng Li (Harmful Algae, 2026)

Structural characterization, cryoprotective potential, and mechanistic insights of thawed drip proteolytic peptides - Xiaoyu Han; Jinxuan Cao; Shiqi Liu; Jinpeng Wang; Wendi Teng; Ming Li; Xianqi Yao; Bambang Kuswandi; Bayu Taruna Widjaja Putra; Ying Wang; Yuemei Zhang (Food Chemistry, 2026)

Tailoring curdlan microgel properties via thermal pretreatment: From gel fracture behavior to fat replacement in low-fat mayonnaise - Jingwen Zhao; Peng Wu; Li Xu; Jian He; Jun Xu; Ying Xu; Yiping Cao; Xiaoyang Li; Yiguo Zhao; Yapeng Fang (Food Hydrocolloids, 2026)

Meta-analysis of environmental-induced changes in optimal nitrogen rate of wheat at regional scale in China - Ying Meng; Xueqin Liu; Yue Li; Linghan Huang; Xu Tian; Syed Tahir Ata-Ul-Karim; Kang Yu; Hainie Zha; Xiaojun Liu; Yongchao Tian; Yan Zhu; Weixing Cao; et al. (Field Crops Research, 2026)

Bio-template synthesis of graphitized carbon-decorated Fe2O3 hierarchical tubes for high-response and low-temperature H2S detection - Ming-Yan Cao; Hui-Nan Lei; Hui-Ye Jiang; Ya-Nan Li; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2026)

Synergistic Effects of Selenium and CaAl-LDHs on Cadmium Detoxification in Brassica Chinensis L.: Physiological and Transcriptomic insights - Xinying Zhang; Yan Liu; Zhiqun Chen; Beibei Li; Xiaoyan Liu; Ying Hao; Tiehua Cao; Xiaoliang Mi; Yizhuo He (Journal of Plant Growth Regulation, 2026)

Synergistic importance of memory and spatial neighbourhood effects in modelling net ecosystem productivity - Jian Liu; Tao Zhou; Jingyu Zeng; Jingzhou Zhang; Xuemei Wu; Yajie Zhang; Qi Zhang; Yancheng Qu; Peixia Liu; Wenjuan Zhang; E Tan; Ying Yu; et al. (Agricultural and Forest Meteorology, 2026)

Field and simulation experimental study on the fracturing of hard rock using electromagnetic pulse stress waves - Chenxu Cao; Yiqiang Lu; Ying Zhu; Jianbin Li; Jianxing Liao (Tunnelling and Underground Space Technology, 2026)

Development and evaluation of a nanozyme-based lateral flow assay strip for avian leukosis virus detection - Liyan Cao; Kexiong Wang; Jie Wang; Xiaoying Jin; Bin Li; Xiaomei Wang; Ying Shen; Rui Zeng; Kai Li (The Veterinary Journal, 2026)

Overexpression of OsFH2 enhances cadmium tolerance and reduces grain cadmium accumulation in rice through synergistic root sequestration and antioxidant defense activation - Xinxin Xu; Shuchang Zhang; Qingxian Mo; Zebin Cai; Yao Cao; Ying Luo; Hongjie Chen; Fangbai Li; Jicai Yi (Journal of Hazardous Materials, 2026)

Process parameter optimization for greenhouse gas mitigation during green-waste composting and mechanistic insights from microbe–environment networks in treatments with contrasting outcomes - Xiaowen Li; Min Cao; Wenyuxin Huang; Hao Mei; Pan Luo; Ping Ma; Junhao Zhang; Weiqin Zhu; Miaomiao He; Ying Ding (Journal of Cleaner Production, 2026)

Moringa oleifera leaves water extract as a novel therapeutic agent for hyperlipidemia prevention: Integrated analysis of bioactive components and metabolic regulatory pathways - Jiaohan Zhan; Jiahong Wang; Li Jiang; Jiahe Li; Jiangxin Li; Juan Cao; Yiyang Du; Tingxu Yan; Ying Jia; Bosai He (Food Research International, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Three new flavonoid glycosides from the herbaceous stems of Ephedra intermedia - Ying Niu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Di Lu; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Product Research, 2026)

A no-till maize seeding technique for conservation agriculture in drip irrigation environments - Panpan Yuan; Xingliang Zhu; Xuejun Zhang; Changjie Han; Jia You; Xinpeng Cao; Ying Chen; Hongwen Li (Computers and Electronics in Agriculture, 2026)

NnLOX1-mediated aroma formation in lotus (Nelumbo nucifera) through multi-omics integration and machine learning - Longyun Cao; Ying Xin; Zifu Ni; Linjie Song; Zongyou He; Peng Jia; Zhixin Zhai; Hao Li; Chen Dong (Food Chemistry, 2026)

Substrate-driven microbial diversity and functional potential of plastisphere biofilms in a dynamic coastal ecosystem of northeastern Taiwan - Priyanka Muthu; Sakcham Bairoliya; Gowri Krishna Girija; Li-Chun Tseng; Bin Cao; Jiang-Shiou Hwang; Ying-Ning Ho (Environmental Pollution, 2026)

High-resolution chronostratigraphic framework and spatiotemporal evolution of Carboniferous-Permian source rocks in the Junggar Basin and its periphery - Zhangshuai Hou; Xiangdong Wang; Dongming Zhi; Yong Tang; Qiong Wu; Hua Zhang; Jian Cao; Dongsheng Xiao; Guobin Fu; Menglin Zheng; Xuefeng Qi; Yaofeng Cai; et al. (Science China Earth Sciences, 2026)

The antidepressant potential of saffron (Crocus sativus L.): molecular mechanisms, neurotransmitter modulation, gut-brain axis interactions, and clinical efficacy in major depressive disorder - Zhenzhen Lai; Yingying Cao; Yu Zhang; Yancui Cai; Sale Zhang; Ying Li; Haifang Wang; Sima-sadat Sabihi (Phytochemistry Reviews, 2026)

Resilience of coastal human-environment composite systems of the 21st century maritime silk road: Theory, model, and spatial patterns - Jie Zhong; Yongchao Liu; Luodan Cao; Chao Ying; Chi Zhou; Yiyu Cao; Hongjia Chen; Jialin Li (Marine Pollution Bulletin, 2025)

Sensitive and selective detection of chromium (VI) via static quenching using a graphene quantum dots/bismuth oxybromide/graphitic carbon nitride (GQDs/BiOBr/g-C3N4) fluorescent probe - Yuankun Liu; Yeqian Huang; Yuanqi Cao; Xinxia Zhang; Ying Wang; Xing Li (Journal of Environmental Chemical Engineering, 2025)

Dual roles of atrazine as an organic contaminant and indicator of intermediate oxidants during sulfite activation of permanganate - Qin Guo; Ying Cao; Jin Jiang; Juan Li (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar” [Food Res. Int. 175 (2024) 113742] - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2025)

Synergetic phase transition suppression and air-stability engineering in layered cathode materials for sodium ion batteries - Li-Feng Zhou; Hao Wang; Lei Cao; Li-Ying Liu; He Jia; Yi-Song Wang; Tao Du (Chemical Engineering Journal, 2025)

Multifunctional MXene-based nanosheets with self-supply oxygen capability for combination tumor therapy - Qianqian Qiao; Ziying Zhang; Jingyu Wang; Tao Liao; Ying Kuang; Yun Liu; Cao Li (Chemical Engineering Journal, 2025)

Higenamine Hydrochloride Attenuates Neuroinflammation in Type I Diabetic Mice by Inhibiting the CRTC2-CREB Signaling Pathway via PAK4 - Ying Li; Lei Wang; Yan Cao; Hujing Lu; Jiawen Zhou; Panpan Zhao; Xinying Guan; Zibo Dong (Molecular Neurobiology, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Progress and Prospects of Transdermal Treatment of Allergic Skin Diseases with Natural Drugs based on Nanotechnology - Wenfei Lu; Jiansheng Cao; Ying Lv; Meng Li; Ye Tang; Yufei Feng (AAPS PharmSciTech, 2025)

Near-congruent Li isotope signature from weathering and erosion of a tectonically active mountain range - Yadan Hu; Fei Zhang; Zhangdong Jin; Ying Xie; Li Deng; Yumei Peng; Chen Chen; Yang Cao; Yongtao Wang; A. Joshua West (Geochimica et Cosmochimica Acta, 2025)

Germplasm-specific phenolic signatures in pear leaves: Comparative variation profiling via UPLC-MS/MS - Hongliang Huo; Jing Li; Zimao Ye; Luming Tian; Xingguang Dong; Jiayu Xu; Ying Zhang; Dan Qi; Chao Liu; Zhiqin Zhou; Yufen Cao (Food Chemistry, 2025)

Investigation of the solid-state fermentation of Astragalus membranaceus residue with Cordyceps militaris: effects on phenolic profile and in vitro neuroprotective activity - Qiaona Wang; Lu Li; Liyun Hu; Ying Cao; Yutong Cao; Jiayi Gao; Honglin Zhang; Feng Zhou; Yulong Wu; Shengjie Li; Renlei Wang (Food Chemistry, 2025)

Application of a novel patulin degradation enzyme PgSDR-A5D9S1 - Yebo Wang; Ke Li; Xulei Ni; Minjie Zhang; Zhehan Cao; Ying Luo; Xinyi Liu (Food Bioscience, 2025)

Oral immunization with a DNA vaccine encoding capsid protein and IFN-γ provokes efficient and long-term immunity against nervous necrosis virus - Haihua Peng; Chen Zhang; Chunze Shang; Caoying Wei; Ying Wu; Zhenjie Cao; Pengfei Li; Yongcan Zhou; Yun Sun (Fish & Shellfish Immunology, 2025)

Solar-driven interfacial evaporator based on modified black phosphorus nanosheets for desalination and water purification - Mengnan Qu; Jin Zhang; Jiehui Li; Yuhang Gao; Ying Zhang; Pu Feng; Menglin Zhu; Mengge Cao; Zaiwen Yang; Jinmei He (Desalination, 2025)

m6A-REFII: an antibody-independent tool for in situ visualizing cellular specific RNA m6A compatible with protein immunofluorescence staining - Yujie Mi; Chenyang Huang; Donghong Liu; Tengwei Li; Xiner Ying; Jie Cao; Jianzhao Liu (Science China Life Sciences, 2025)

DTX1 Modulates Microglial M1 Polarization and Exacerbates Neuroinflammation in Traumatic Brain Injury Model Rats through NF—κB/IRF5 - Yonghui Zhang; Zongxing Zou; Rongwei Li; Xiaochuan Fu; Ganyu Li; Lu Wang; Yan Zhang; Yuyu Chen; Zuzhi Chen; Dongfang Yang; Yan Jiao; Weiguang Zhang; et al. (Molecular Neurobiology, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Highly salt-resistant and all-day solar-driven interfacial evaporator based on Janus CS@Fe3O4/SA-MF - Jinmei He; Yuhang Gao; Jiehui Li; Ying Zhang; Menglin Zhu; Jin Zhang; Mengge Cao; Xiao Wei; Mengnan Qu (Journal of Environmental Chemical Engineering, 2025)

Releasing ACE-inhibitory peptides from walnut protein via pulsed electric field: A multiscale mechanism-structure-function investigation - Xueying Song; Siliang Wu; Chenchen Cao; Yihan Mu; Ying Li; Ruili Liu; Guowan Su (Innovative Food Science & Emerging Technologies, 2025)

Enhanced acidic hydrogen evolution stability and activity in CoP through S doping for proton exchange membrane electrolyzers - Shiqing Zhang; Shaokai Ma; Zihao Wang; Zihang Cao; Fang Liu; Ying Li; Xuewen Xu; Yuanhui Ma; Yanming Xue; Chengchun Tang; Jun Zhang (Fuel, 2025)

Multi-electron donation promotes the photocatalytic conversion of carbon dioxide to methane in a covalent bonded metal-complex/quantum dots hybrid catalyst - Qian Zhao; Mohamed Abdellah; Yang Liu; Jie Meng; Xianshao Zou; Kasper Enemark-Rasmussen; Yu Zhou; Yi Li; Yuehan Cao; Yijiang Chen; Nora Eliasson; Ying Zhou; et al. (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Hydrogen spillover by boron carbon nitride support for efficient acidic hydrogen evolution reaction - Fang Liu; Shiqing Zhang; Shaokai Ma; Zihang Cao; Ying Li; Yuanhui Ma; Xuewen Xu; Jun Zhang; Yanming Xue; Chengchun Tang (Chemical Engineering Journal, 2025)

Direct electron transfer from electron-reservoir sandwich-type polyoxometalate to Co2Ni2-cluster via water-assisted proton channels and tandem effects for efficient nitrate-to-ammonia electrocatalysis - Jiaxing Li; Mengle Yang; Aixiang Tian; Xixian Cao; Jun Ying; Xiuli Wang (Chemical Engineering Journal, 2025)

Dual-regulation of high-valence metals and oxygen vacancy enabled direct electrocatalytic amines oxidation via constructing a M6+-OV-Ni/Co3+ active pocket - Guosheng Wang; Jingzhou Wang; Wenyue Lin; Huilin Li; Haiyang Yu; Xiaohui Liu; Wenjie Zhang; Ying Cao; Xiantai Zhou; Can Xue (Chemical Engineering Journal, 2025)

Efficient degradation and deiodination of iopamidol by synergistic •OH and SO4•− oxidation in O3/PMS system - Xing Wang; Guanqi Liu; Ying Cao; Xinglin Lu; Chaoting Guan; Juan Li; Jun Ma; Jin Jiang; Yi Yang (Chemical Engineering Journal, 2025)

Thrombectomy in Stroke Patients with Large Vessel Occlusion and Mild Symptoms: Insights from a Multicenter Observational Study - Kai Qiu; Yu Hang; Penghua Lv; Ying Liu; Mingchao Li; Liandong Zhao; Qijin Zhai; Jinan Chen; Zhenyu Jia; Yuezhou Cao; Linbo Zhao; Haibin Shi; et al. (Translational Stroke Research, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Land surface temperatures outperform gridded air temperatures in modeling forest growth across the Northern Hemisphere - Feiyu Yang; Yujiu Xiong; Wenjin Wang; Hongxing Hu; Mantik Lai; Chao Zhang; Jiahao Cao; Leyao Zhu; Qibo Fan; Ying Zhao; Zhou Wang; Yaling Zhang; et al. (Agricultural and Forest Meteorology, 2025)

WSSV Infection in the Gut Microbiota of the Black Tiger Shrimp Penaeus monodon - Youhong Wang; Xiaolu Wang; Chunlei Gai; Yuanyuan Li; La Xu; Shuxian Wang; Li Li; Xiaoqing Yu; Ranghui Fu; Jing Diao; Haibin Ye; Ying Fan; et al. (Fishes, 2025)
This study investigated the impacts of white spot syndrome virus (WSSV) on the gut microbiota of Penaeus monodon through a comparative microbiota analysis of infected and healthy shrimp using 16S rDNA sequencing. The WSSV-infected shrimp exhibited characteristic white spots, reduced feeding activity, and behavioral lethargy preceding 100% mortality. The comparative microbiota analysis revealed a significantly diminished α-diversity in the infected specimens, marked by phylum-level dominance shifts from Proteobacteria (72.68%) and Firmicutes (11.27%) in the controls to Cyanobacteria (75.51%) and Proteobacteria (15.63%) in the WSSV-infected shrimp. An LEfSe analysis identified Arthrospira_PCC-7345 and Halochromatium as significantly enriched taxa during infection, contrasting with depleted populations of Ruegeria, Marivita, Bacillus, and seven other genera. The distinct dysbiosis pattern characterized by the pathogen-favored taxa proliferation and commensal species suppression demonstrates WSSV-associated microbiota restructuring, potentially contributing to disease progression in farmed P. monodon. These findings establish intestinal microbial biomarkers for early WSSV detection in aquaculture systems.

Enhancing the participation of water in the anaerobic digestion of sewage sludge for highly efficient methanogenesis - Jiachang Cao; Ying Xu; Chen Zhang; Xiang Li; Rui Liu; Xueye Wang; Xiaohu Dai (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

“Cuckoo in the nest”: L-arginine promoted the migration of Na+ to ameliorate the gel quality of low salt fish balls - Yuanxiu Liu; Tong Shi; Xiyue Cao; Xin Wang; Mengzhe Li; Chenya Lu; Xiaoli Zhang; Ying Tian; Li Yuan; Wengang Jin; Ruichang Gao (Food Chemistry, 2025)

Preparation and characterization of a starch-based active packaging with pH-sensitive release via tea tree essential oil loaded in a covalent organic framework - Peiqin Cao; Yiping Song; Dongliang Jin; Yuxia Zhang; Panliang Zhang; Kewen Tang; Ying Li; Rongrong Wang; Kang Zhang (Food Chemistry, 2025)

Converting pig manure into biochar mitigates the antibiotic resistance of vegetable endophytes - Xue Zhou; Jun Ma; Min Qiao; Yin Wang; Zhi-Hong Cao; Jian-Qiang Su; Wan-Ying Xie; Patrick O'Connor; Gang Li (Environmental Pollution, 2025)

Dry reforming of methane by La2NiO4 perovskite oxide: Cordierite-ceramic-supporting monolithic catalyst with Cu B-site substitution improving reacting performance - Dingshan Cao; Zhen Qin; Cong Luo; Xiaoshan Li; Zhaowei Shi; Fan Wu; Ying Zheng; Liqi Zhang (Chemical Engineering Journal, 2025)

Soil organic carbon content and stability of different cropping patterns depends on the distribution and stability of aggregates in the hilly area of central Sichuan basin - Yong Chen; Yingqi Li; Gaozi Zhou; Ying Liu; Tao Cao; Guoke Wang; Junsheng Wang; Haixian Jiao; Huifang Xiao; Sixi Liu; Wei Zhou; Fei Deng; et al. (Agriculture, Ecosystems & Environment, 2025)

Collagen alpha-5(IV) chain activation by nuclear factor 1/C promotes nasopharyngeal carcinoma progression - Ying Cao; Peibei Wang; Peng Li; Kai Wei; Xinle Kang; Xiao Han; De Huai; Bing Fei (Human Cell, 2025)

Isolation, Identification, and Virulence Properties of Enterobacter bugandensis Pathogen from Big-Belly Seahorse Hippocampus abdominalis - Haibin Ye; Chenhao Teng; Yueqi Yang; Yiyao Liu; Li Li; Ying Fan; Youhong Wang; Jing Diao; Lingling Yu; Chunlei Gai; Haipeng Cao (Fishes, 2025)
Nowadays, members of the genus Enterobacter have been documented as human and aquaculture pathogens. To date, no reports have described Enterobacter bugandensis infecting Hippocampus abdominalis. In the present study, an isolate of E. bugandensis, designated H4, was identified as a causative pathogen in cultured H. abdominalis following Koch’s postulate, and its virulence properties were further described. The isolate’s genome consisted of a single circular chromosome and harbored several virulence and resistance genes, including, but not limited to, csgG, acrB, hcp, gndA, galF, rpoS, fur, rcsB, and phoP involved in adherence, antimicrobial activity, effector delivery systems, immune modulation, and regulation, as well as baeR, blaACT-49, ramA, hns, ftsI, acrA, gyrA, fabI, crp, oqxB, parE, gyrB, phoP, rpoB, tuf, ptsI, and fosA2 functioning against aminoglycoside, cephamycin, disinfecting agent and antiseptic, fluoroquinolone, macrolide, peptide, and other antimicrobials. Additionally, the isolate exhibited multiple resistance to cephalosporins, penicillins, and tetracyclines and demonstrated a median lethal dose (LD50) of 4.47 × 105 CFU/mL in H. abdominalis. To our knowledge, this is the first study to describe E. bugandensis infecting H. abdominalis. These findings highlight the zoonotic potential of E. bugandensis and underscore the need for targeted health management in seahorse farming.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Fabrication of fucoxanthin-loaded composite nanoparticles based on lactoferrin and carboxymethyl chitosan: Interaction mechanism, stability and the application in filled hydrogel beads - Wen Jiang; Xinyu Cao; Ying Guan; Tingting Zeng; Juxiu Li (Food Research International, 2025)

In silico identification for flavor antioxidant compounds in Chrysanthemi flos uncovers the interactions between saccharides and secondary metabolites - Jiamu Ma; Le Wang; Mingxia Li; Jianling Yao; Wei Liu; Feng Zhang; Mengyu Sun; Yu Cao; Yuqing Yang; Yongqi Yang; Letian Ying; Meng Shen; et al. (Food Chemistry, 2025)

Bone marrow microenvironment-targeted yolk-shell nanoparticle enhances acute myeloid leukemia chemotherapy by preventing endothelial cell/ECM-mediated adhesion - Shiyi Hong; Pei Peng; Yutian Huang; Siying Cai; Cao Yao; Tongtong Huang; Yulu Ying; Wei Li; Yang Xiong; Mancang Gu; Guilin Cheng; Chaofeng Mu (Chemical Engineering Journal, 2025)

Inter-model comparison of the DRI-2001 and DRI-2015 for carbonaceous aerosol analysis in PM2.5: Method development and application in Chongqing - Chao Peng; Chongzhi Zhai; Yang Chen; Mi Tian; Ying Xiang; Tianyu Zhai; Weikai Fang; Xin Long; Xiaocheng Wang; Mulan Chen; Yunqing Cao; Min Du; et al. (Atmospheric Pollution Research, 2025)

The molecular mechanism for improvement of coastal silt soil by the intercropping model of Suaeda glauca (Bunge) Bunge and Sesbania cannabina (Retz.) Pers - Xiaochi An; Ying Li; Yinhua Cao; Zaifeng Wang; Min Xu; Bin Lian (Plant and Soil, 2025)

Enhanced complexity of interkingdom co-occurrence networks in blueberry rhizosphere microbial communities under soil pH stress - Jilu Che; Yaqiong Wu; Hao Yang; Ying Chang; Wenlong Wu; Lianfei Lyu; Xiaomin Wang; Fuliang Cao; Weilin Li (Applied Soil Ecology, 2025)

Companion animals as sources of hazardous critically important antimicrobial-resistant Escherichia coli: Genomic surveillance in Shanghai - Yiwen Chen; Min Li; Bingqing Sun; Luming Xia; Yifei Zhang; Jun Feng; Min Chen; Zile Cheng; Chao Lv; Weiye Chen; Jiewen Huang; Qingtian Li; et al. (Journal of Hazardous Materials, 2025)

Absorption and transport mechanism of heme chloride/gamma-cyclodextrin inclusion complexes - Li Huang; Haoxin Li; Jinpeng Wang; Wendi Teng; Ying Wang; Yuemei Zhang; Jinxuan Cao (Food Bioscience, 2025)

Key toxic pathways of hepatotoxicity induced by titanium dioxide nanoparticles through multi-omics analysis - Jiaqi Shi; Ying Ma; Nairui Yu; Yi Zhang; Zongfu Cao; Li Guan; Xiaodong Liu; Zhangjian Chen; Guang Jia (Food and Chemical Toxicology, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Driving factors and interactions of urban transportation carbon emissions: A case study of China - Jiangjun Wan; Xiong Wu; Yuye Li; Zhonglin Li; Kuntao Deng; Jiaqi Zeng; Xinrui Fan; Ying Cao (Transportation Research Part D: Transport and Environment, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Spring festival firework activities exacerbate toxic effects of aerosol essential components - Uudam Hu; Ying Sun; Guoqing Yang; Mingqi Liu; Yue Gao; Liu Lin; Yingnan Cao; Wei Liu; Yaoqiang Huo; Jianguo Liu; Qing Li (Journal of Hazardous Materials, 2025)

Mechanistic impact of organics on electro-induced transformation of iron oxides and simultaneous uranium immobilization in wastewater - Mi Li; Dan Huang; Lanlan Cao; Sheng Liu; Xiaoyan Wu; Zhaowen Cheng; Xiaowen Zhang; Yilong Hua; Ying Peng; Qi Fang; Tao Cai (Journal of Hazardous Materials, 2025)

Emission pathways and reduction strategies of greenhouse gases in coal chemical industry: A review - Guoqing Yang; Jucai Yang; Uudam Hu; Mingqi Liu; Yanli Lv; Yunping Han; Tianlong Zheng; Yingnan Cao; Ying Zhu; Wei Liu; Yaoqiang Huo; Jianguo Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

LC-MS/MS-based metabolomics and multivariate statistical analysis reveal the mechanism of yeast extracellular proteases on myofibrillar protein degradation, metabolite development and sensory characteristics improvement - Danni Li; Yiqi Liang; Qiang Xia; Daodong Pan; Lihui Du; Jun He; Yangying Sun; Ying Wang; Wei Wang; Jinxuan Cao; Changyu Zhou (Food Microbiology, 2025)

Dynamic reconstruction Engineering of Nickel(II) carbonate hydroxide for enhanced electrocatalytic alcohol oxidation - Lihao Liu; Suiqin Li; Kai Li; Jiahui He; Yuhang Wang; Jieyu Wang; Ying Chen; Yinjie Xu; Mengxin Wang; Yongyong Cao; Xing Zhong; Jianguo Wang (Chemical Engineering Journal, 2025)

Corrigendum to “A highly sensitive and reusable magnetic nano-electrochemical biosensor for the detection of the liver cancer biomarker heat shock protein 70” [Chem. Eng. J. 505 (2025) 159860] - Ruming Liu; Ying Li; Yan Liu; Yixuan Wang; Qiuyue Si; Dorothy Araba Yakoba Agyapong; Juan Feng; Ruiqin Fang; Lixia Tang; Fei Cao; Hongjuan Zeng (Chemical Engineering Journal, 2025)

Using quantitative evaluation model to assess the environmental benefits of metabolites in flax retting wastewater aerobic compost: The trade-offs of core species build the profiles of beneficial and harmful metabolites converted from lignocellulose - Ying Yang; Zhichao Yang; Jie Kang; Zhenchao Wu; Yangcun Sun; Xinbo Cao; Yuhao Guo; Xiujun Tu; Liangyang Mao; Shuo Li; Weige Yao; Jingping Ge; et al. (Chemical Engineering Journal, 2025)

Enhancing genetic transformation efficiency of melon (Cucumis melo L.) through an extended sucrose-removal co-culture - Xiang Li; Chenchen Cao; Ying Liu; Pablo Bolaños-Villegas; Jiyu Wang; Ranran Zhou; Juan Hou; Qiong Li; Wenwen Mao; Panqiao Wang; Lili Li; Chen Luo; et al. (Plant Cell Reports, 2025)

Resolving taxonomic complexities in medicinal Aralia: Genome-scale phylogeny and super-barcoding advance species identification and conservation - Yanan Cao; Menghao Wang; Jiamei Li; Ying Yang; Hao Wang; Yanyan Liu; Hongwei Wang; Risong Na (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Differences in starch and protein composition, morphological and structure, and their impacts on eating quality of soft japonica rice under different light and nitrogen fertilizer conditions in southern China - Zhongtao Ma; Jianghui Yu; Xi Chen; Jiale Cao; Ying Zhu; Guodong Liu; Guangyan Li; Fangfu Xu; Qun Hu; Hongcheng Zhang; Haiyan Wei (Food Chemistry, 2025)

Low-frequency ultrasound-driven piezoelectric films repair neuro-immune circuits in diabetic wound healing - Chenyan Yu; Ying Hu; Xin Zhang; Kaixu Yu; Lang Chen; Wenqian Zhang; Shengming Zhang; Zhenhe Zhang; Ruiyin Zeng; Yuheng Liao; Yanzhi Zhao; Lin Gan; et al. (Chemical Engineering Journal, 2025)

Fully recyclable flame-retardant PLA composites with balanced performance based on a phosphorus/nitrogen-containing zwitterion - Qiang Zhang; Xing Cao; Yan-Peng Ni; Li-Ping Zhang; Zhao Ding; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Identification of multiple foodborne pathogens using single-atom nanozyme colorimetric sensor arrays and machine learning - Ying Li; Feng Chen; Yiping Liu; Muhammad Arif Khan; Hongbin Zhao; Hongmei Cao; Daixin Ye (Chemical Engineering Journal, 2025)

Validation of CRISPR construct activity and gene function in melon via a hairy root transformation system - Xiang Li; Chenchen Cao; Pablo Bolaños-Villegas; Ying Liu; Jiyu Wang; Qiong Li; Wenwen Mao; Panqiao Wang; Juan Hou; Lili Li; Jianbin Hu; Yonghua Li (Physiology and Molecular Biology of Plants, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Porcine antibodies reveal novel non-neutralizing universal epitopes on FMDV and their overlaps with neutralization sites - Ying Sun; Shenglin Huang; Fengjuan Li; Shulun Huang; Pinghua Li; Qiongqiong Zhao; Tao Wang; Huifang Bao; Yuanfang Fu; Pu Sun; Xingwen Bai; Hong Yuan; et al. (Veterinary Microbiology, 2025)

Assemble a removable dual-function solar photothermal evaporator with wetting gradient: Efficient desalination and wastewater treatment - Jinmei He; Yuhang Gao; Jiehui Li; Ying Zhang; Yuqing Wang; Menglin Zhu; Jin Zhang; Mengge Cao; Xiao Wei; Mengnan Qu (Desalination, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Sus scrofa RNase L inhibits PRRSV replication by activation of type I IFN signaling pathway and apoptosis - Xiangju Wu; Xiaoyan Cong; Ping Jiang; Mingming Zhou; Ying Yu; Dandan Jiang; Yue Hu; Juntong Li; Jinxia Zhang; Ying Cao; Haowen Zhang; Yijun Du; et al. (Veterinary Microbiology, 2025)

Exploration on antifreeze potential of thawed drip enzymatic hydrolysates on myofibrillar proteins in pork patties during freeze-thaw cycles - Xiaoyu Han; Yang Li; Ying Wang; Jinpeng Wang; Wendi Teng; Longlong Dong; Yuling Cai; Jinxuan Cao; Yuemei Zhang (Food Chemistry, 2025)

Encapsulation of EGCG by whey protein isolate and β-cyclodextrin nanocomplexes: A strategy to mask the bitter and astringent taste and increase the stability in beverages - Hujun Xie; Han Wang; Min Huang; Ying Gao; Qing-Qing Cao; Hao Li; Qingbo Jiao; Gerui Ren; Yong-Quan Xu (Food Hydrocolloids, 2025)

Impact of polyethylene terephthalate microfibers on histopathological and molecular responses induced by cadmium in the polychaete Perinereis aibuhitensis - Yi Cong; Yisong Jiang; Mingxing Zhang; Shuo Cao; Qi Li; Zhaochuan Li; Fei Jin; Yadi Lou; Ying Wang; Huahong Shi; Juying Wang (Environmental Pollution, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

Air injection in paddy soil reduces N2O and NH3 emissions and regulates the nitrogen cycle - Jichao Tang; Quanyi Hu; Chengfang Li; Cougui Cao; Xuelin Zhang; Ying Zhang; Wenfeng Tan; Bo Cheng; Dongliang Xiong; Tianqi Liu; Yakov Kuzyakov (Soil and Tillage Research, 2025)

Involvement of inorganic nitrogen species ( NO X − (x = 2, 3)) in the degradation of organic contaminants in environmental waters via UV irradiation or chemical oxidation: A dual-edged approach - Jiebin Duan; Ying Cao; Quanzhen Yang; Wenqi Li; Qianqian Huang; Qin Guo; Jin Jiang (Science of The Total Environment, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Large-scale dual-responsive ClO2 controlled-release film for strawberry preservation - Siqi Chen; Wenya Ma; Ying Cao; Kunpeng Qian; Qingfeng Dong; Li Li (Food Chemistry, 2025)

Regional and longitudinal dynamics of human milk protein components assessed by proteome analysis on a fast and robust micro-flow LC–MS/MS system - Junxia Cao; Xinling Cui; Hai Lu; Hui Wang; Wen Ma; Zhan Yue; Kemiao Zhen; Qiaosi Wei; Hongmei Li; Shilong Jiang; Wantao Ying (Food Chemistry, 2025)

Exploring the potential of fibrinogen hydrolysates as enhancers for myofibrillar protein gelation: Insights into molecular assembly behavior - Yuemei Zhang; Genpeng Bai; Ying Wang; Jinpeng Wang; Wendi Teng; Ming Li; Xianqi Yao; Jinxuan Cao (Food Chemistry, 2025)

A highly sensitive and reusable magnetic nano-electrochemical biosensor for the detection of the liver cancer biomarker heat shock protein 70 - Ruming Liu; Ying Li; Yan Liu; Yixuan Wang; Qiuyue Si; Dorothy Araba Yakoba Agyapong; Juan Feng; Ruiqin Fang; Lixia Tang; Fei Cao; Hongjuan Zeng (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

The impact of agricultural land use on the linkages between soil microbial communities and agroecosystem functioning is depth-dependent - Wenchao Cao; Yukun Zou; Gang Li; Ying Shan; Jinchuang Wang; Brajesh Kumar Singh (Agriculture, Ecosystems & Environment, 2025)

Targeted isolation of lignans from the roots of Anthriscus sylvestris (L.) Hoffm. by small molecule accurate recognition technology - Yan-ling Liu; Yan-gang Cao; Ya-juan Zheng; Ying Niu; Lan Chen; Xu Chen; Xin-yi Ma; Xiang-da Li; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Analysis of the softening-melting mechanism of cold-bonded briquette from return sinter fines - Ying Li; Dejin Qiu; Manqing Li; Yuandong Xiong; Timo Fabritius; Su Cao; Ang Li; Abdallah Ahmed Elsherbiny; Jie Ren; Han Wei; Yaowei Yu (Journal of Cleaner Production, 2025)

Perfluorodecanoic acid induces the increase of innate cells in zebrafish embryos by upregulating oxidative stress levels - Juhua Xiao; Dou Yang; Boxi Hu; Wenwen Zha; Weirong Li; Ying Wang; Fasheng Liu; Xinjun Liao; Huimin Li; Qiang Tao; Shouhua Zhang; Zigang Cao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Significantly improving the stability of high-entropy PtFeNiCoMn nanoalloys by nitrogen doping in oxygen electrocatalysis - Mang Niu; Qinhe Guan; Weiyong Yuan; Chun Xian Guo; Dapeng Cao; Chang Ming Li; Lian Ying Zhang; Xiu Song Zhao (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Investigating the role of two-dimensional and three-dimensional urban structures in seasonal surface radiation budget - Jingyi Chen; Shisong Cao; Meng Du; Mingyi Du; Xianglei Liu; Wen Song; Ying Liang; Wen He; Ling Li; Nuan Wang (Building and Environment, 2025)

Factors affecting the different growth rates of PM2.5：Evidence from composition variation, formation mechanisms, and importance analysis of water-soluble inorganic ions with case study in northern China - Huan Li; Ting Zhang; Hui Su; Sui Xin Liu; Ying Qiang Shi; Lu Yao Wang; Dong Dong Xu; Jia Mao Zhou; Zhu Zi Zhao; Qi Yuan Wang; Steven Sai Hang Ho; Yao Qu; et al. (Atmospheric Environment, 2025)

Map-based cloning revealed BhAPRR2 gene regulating the black peel formation of mature fruit in wax gourd (Benincasa hispida) - Xuling Zhai; Jinqiang Yan; Wenrui Liu; Zheng Li; Zhenqiang Cao; Ying Deng; Renlian Mo; Baochen Wang; Xiaoxin Cheng; Dasen Xie; Biao Jiang (Theoretical and Applied Genetics, 2025)

CircHAT1 regulates the proliferation and phenotype switch of vascular smooth muscle cells in lower extremity arteriosclerosis obliterans through targeting SFRS1 - Xian-ying Huang; Fang-yong Fu; Kai Qian; Qiao-li Feng; Sai Cao; Wei-yu Wu; Yuan-lin Luo; Wei-jie Chen; Zhi Zhang; Shui-chuan Huang (Molecular and Cellular Biochemistry, 2025)

Associations between prenatal exposure to metal mixtures and infant reproductive hormones during mini-puberty - Ling Yu; Jiangtao Liu; Ying Li; Shulan Li; Shuting Cao; Fasheng Li; Yuanyuan Li; Hongxiu Liu; Zhenyu He; Shunqing Xu; Wei Xia (Science of The Total Environment, 2024)

Unveiling the formation and influence mechanisms of PCDD/F memory effect in wet scrubbers: Fundamental research and field verification - Ying Peng; Yunfeng Ma; Xiaoqing Lin; Jisheng Long; Li Bai; Hailiang Du; Yang Cao; Jiajun Wang; Lu Liu; Xiaodong Li (Science of The Total Environment, 2024)

Ecological response mechanism of alkaline wastewater periphytic biofilms to pH alteration - Mei Zhong; Li Cao; Chunyan Li; Hansen Xu; Qi Li; Wanying Fu; Ying Lu; Yanjie Zhang; Xia Luo; Xinyou Liu (Journal of Water Process Engineering, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Bioinspired Core-shell nanospheres integrated in multi-signal immunochromatographic sensor for high throughput sensitive detection of Bongkrekic acid in food - Chenyu Xuan; Yuanyuan Cao; Haiyu Wu; Ying Wang; Jia Xi; Kaixuan Ma; Qinlin Feng; Boyang Sun; Huiqi Yan; Li Wang (Food Chemistry, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

In-situ Self-Assembled organic anion interfacial layer on Zn anode surface for boosting the stability of aqueous zinc ion energy storage devices - Yixuan Li; Deyi Zhang; Bing Wang; Yang Li; Zheyuan Li; Youzhi Cao; Zhe Liu; Tiantian Ying; Shiyou Li; Yue Li (Chemical Engineering Journal, 2024)

A Novel Mohr–Coulomb–Matsuoka–Nakai Strength Criterion for Rocks Considering Brittle–Ductile Domain - Jiacun Liu; Junjie Xiao; Xing Li; Zhuokang Cao; Ying Xu (Rock Mechanics and Rock Engineering, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Advanced glycosylation end products promote the progression of CKD-MBD in rats, and its natural inhibitor, quercetin, mitigates disease progression - Yujie Wang; Chenggang Hu; Ling Cao; Qi Liu; Ying Li; Tingting Zhu; Dongmei Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Morpho-histological and Transcriptome Analysis Reveal the Unreduced Sperm Formation Mechanism in cdk1-Depletion Zebrafish - Yunbang Zhang; Rongyun Li; Hui Li; Yuwei Huang; Yihui Mei; Yuxuan Zheng; Yankun Guo; Zihao Zhou; Zhonglin Yong; Ying Zhao; Wenjing Dong; Jian Gao; et al. (Marine Biotechnology, 2024)

Genome-Wide Identification, Characterization, and Expression Analyses of the Mucin Genes in Japanese Flounder (Paralichthys olivaceus) - Ying Zhu; Xinsheng Yang; Xu Yan; Ning Yang; Min Cao; Chengbin Gao; Chao Li (Journal of Ocean University of China, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Niche construction in a bioelectrochemical system with 3D-electrodes for efficient and thorough biodechlorination - Deping Li; Wenbo Guo; Bo Chen; Ying Zhai; Yi Lang; Tianbao Guo; Xinde Cao; Ling Zhao (Water Research, 2024)

Shale gas leakage and fault activation: Insight from the 2021 Luxian MS 6.0 earthquake, China - Zhaofei Liu; Zhi Chen; Ying Li; Zhidan Zhao; Shunying Hong; Le Hu; Ling Ma; Chang Lu; Yuanxin Zhao; Hongyi He; Shujuan Su; Ying Zhao; et al. (Tectonophysics, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Reconstructing the rapid transitions of ecosystems during the mid-late Holocene: A pollen record from Haixing wetland in Bohai Bay, North China - Yihang Cao; Yawen Ge; Siyu Wang; Baoshuo Fan; Changhong Liu; Hanfei You; Rongrong Wang; Ying Wang; Zhen Zhang; Shengrui Zhang; Cange Li; Yuecong Li (Quaternary Science Reviews, 2024)

Metabolism of nitrogen and sulfamethoxazole, performance recovery mechanism, and antibiotic resistance genes (ARGs) behaviors in membrane aerated biofilm reactor (MABR) - Ting Li; Xiwei Cao; Lijun Gu; Ying Cui; Xinglin Li; Yi Li; Sher Jamal Khan; Baoan Li; Shuo Zhang (Journal of Cleaner Production, 2024)

Visible-light-driven photobiocatalytic synthesis of chiral sulfoxides over immobilized chloroperoxidase on magnetic yolk–shell Fe3O4@Cu-H-TiO2 photocatalyst - Xiaoyang Yue; Yuying Hou; Cuiyao Cao; Xue Cao; Haolei Song; Yanjun Jiang; Liya Zhou; Ying He; Xiaobing Zheng; Li Ma; Shijie Li (Journal of Cleaner Production, 2024)

A high-permeability method for extracting purple yam saponins based on ultrasonic-assisted natural deep eutectic solvent - Yu-Jiao Hou; Peng-wei Wang; Han Zhang; Ying-Ying Fan; Xu Cao; Yan-Qiong Luo; Qian Li; Mosesmanaanye Njolibimi; Wen-jing Li; Bo Hong; Chun-jie Zhao (Food Chemistry, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Oxidation enhances the toxicity of polyethylene microplastics to mouse eye: Perspective from in vitro and in vivo - Ying Yang; Ji Wang; Yongpeng Shi; Hanwen Cao; Li Wei; Lan Gao; Mingxin Liu (Environmental Pollution, 2024)

Emerging magnetic-responsive hydrogel actuators with anisotropic shape for intracardiovascular directional motion - Yue Cao; Yuming Li; Wenbin Lu; Sunlong Li; Zheng Mao; Zhiwei Jiang; Ying Wang; Weipeng Lu; Qing He; Liqun Zhao; Cihui Liu; Xuguang Li; et al. (Chemical Engineering Journal, 2024)

Advanced design of metal single-atom (Pt, Mn, Fe or Cu) loaded S-Ni(OH)2 nanosheets array catalysts to achieve high-performance overall water splitting - Wenhui Fang; Tingting Tang; Min Li; Shixian Xin; Ying Wu; Yutao Cao; Zhize Yu; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Exploring the remarkable effects of microwave treatment on starch modification: From structural evolution to changed physicochemical and digestive properties - Mengdi Cai; Yu Zhang; Hongwei Cao; Sen Li; Ying Zhang; Kai Huang; Hongdong Song; Xiao Guan (Carbohydrate Polymers, 2024)

Sulfate-reducing consortium HQ23 stabilizes metal(loid)s and activates biological N-fixation in mixed heavy metal-contaminated soil - Houquan Liu; Jun Yao; Chunyu Shi; Robert Duran; Jianli Liu; Shun Jiang; Miaomiao Li; Wancheng Pang; Bo Ma; Ying Cao; Geoffrey Sunahara (Science of The Total Environment, 2024)

Metabolites of blueberry roots at different developmental stages strongly shape microbial community structure and intra-kingdom interactions at the root-soil interface - Jilu Che; Yaqiong Wu; Hao Yang; Ying Chang; Wenlong Wu; Lianfei Lyu; Xiaomin Wang; Fuliang Cao; Weilin Li (Science of The Total Environment, 2024)

Two undescribed monoterpenoids from the fruit of Gardenia jasminoides Ellis - Di Lu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Ying Niu; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Improving the storage quality of Harbin red sausages by quaternized chitosan/sodium alginate coating curcumin nano-emulsion - Ying-ao Zhu; Fei Li; Meihui Wang; Yuhang Cao; Baohua Kong; Qian Liu; Hui Wang; Qian Chen (Meat Science, 2024)

Catalytic oxidation of toluene-acetone mixture over MnOx/Cu foam monolithic catalyst: Strong Cu-Mn interaction and amorphous phase - Ying Huang; Juan Lei; Baobao Bai; Xiaoli Ren; Lijun Cheng; Yu Cao; Shuang Wang; Jinping Li (Journal of Environmental Chemical Engineering, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

In-situ rapid cultivation of aerobic granular sludge in A/O bioreactor by using Ca(ClO)2 pretreating sludge - Tingting Cao; Yue Yang; Xiaomeng Li; Liang Liu; Xiyang Fei; Yuanhang Zhao; Leilei Zhang; Ying Lu; Dandan Zhou (Bioresource Technology, 2024)

Influence of scion cultivar on the rhizosphere microbiome and root exudates of Phaseolus vulgaris in grafting system - Xiuli Wei; Yuanyuan Cui; Jiaqi Wang; Guoyuan Song; Ying Cao; Long Liu; Zhixin Liu; Jing Yang; Chen Li; Jiao Wang; Moran Li; Xiao Xiao (Plant and Soil, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Nucleophilic hydrolysis of dichloroacetonitrile and trichloroacetonitrile disinfection byproducts by peroxymonosulfate: Kinetics and mechanisms - Yangyi Yu; Juan Li; Junhui Zhou; Ying Cao; Qin Guo; Yongze Liu; Yi Yang; Jin Jiang (Chemosphere, 2024)

Effective amendment of cadmium in water and soil before and after aging of nitrogen-doped biochar: Preparation optimization, removal efficiency and mechanism - Yifan Wang; Jianen Li; Qiaona Li; Liang Xu; Yunhe Ai; Wei Liu; Yutong Zhou; Boyu Zhang; Nan Guo; Bo Cao; Jianhua Qu; Ying Zhang (Journal of Hazardous Materials, 2024)

Greenhouse gas, water, and economic implications of permeable pavements: Quantification for pilot sponge cities in China - Ying Wei; Xinyu Cao; Jianing Li; Yuan Chang (Journal of Cleaner Production, 2024)

Fe(II)-mediated Fe–N–P metabolism in an anammox-dominated system for enhanced nitrogen removal and Fe–P crystals (FePs) production - Biru Zhou; Lan Lin; Qian Zhang; Ying Wang; Zikun Zhang; Xiaoqing Xie; Wenzhi Cao; Yu-You Li; Yanlong Zhang (Journal of Cleaner Production, 2024)

Perovskite-structured ultrasensitive CaMnO3 nanoenzyme enables highly efficient ultrasound-amplified and catalysis-involved synergistic tumor therapy - Ying Wang; Xinyue Cao; Xiaoyan Li; Liang Chen; Meiqi Chang; Yu Chen; Bingcang Huang (Chemical Engineering Journal, 2024)

Electro-mechano transduction of stacked triboelectric nanogenerator considering wave force: Modeling, validation and applications - Chen Cao; Fan Shen; Chuanfu Xin; Qin Zhang; Qiwei Zheng; Ying Gong; Heming Liu; Yan Peng; Zhongjie Li (Chemical Engineering Journal, 2024)

Copper phosphate-rotenone nanocomposites for tumor therapy through autophagy blockage-enhanced triphosadenine supply interruption and lipid peroxidation accumulation - Yi Ouyang; Ying Li; Chunmei Chen; Sheng Zhao; Mengyuan Wu; Benqing Zhou; Yang Cao; Hui Liu (Chemical Engineering Journal, 2024)

Stabilized Nickel-Rich oxide cathode by the confining effect of Nb lattice anchoring and epitaxial shielding layer - Tangzhe Cao; Hang Fan; Ying Lei; Jianying Li; Weifeng Fan; Bin Zhang; Xingyong Liu; Tinghong Huang; Yun Zhang (Chemical Engineering Journal, 2024)

The secondary visual cortex mediated the enhancement of associative learning on methamphetamine self-administration behaviors - Cai-ling Wang; Dan-ni Cao; Ning Wu; Ying-jie Zhu; Jin Li (Psychopharmacology, 2024)

Simulated Yak and Tibetan Sheep Urine Deposition Fleetingly Promoted N2O, CO2 and CH4 Emissions in an Alpine Steppe of Northern Xizang Plateau - Jiaxiu Li; Xiaodan Wang; Jian Sun; Jiangtao Hong; Xiaoke Zhang; Ziyin Du; Jing Du; Zhaoyang Xiong; Xue Zhang; Ying Cao; Shuang Wang (Journal of Soil Science and Plant Nutrition, 2024)

Turbulent atmospheric phase correction for SBAS-InSAR - Meng Duan; Zhiwei Li; Bing Xu; Weiping Jiang; Yunmeng Cao; Ying Xiong; Jianchao Wei (Journal of Geodesy, 2024)

Ultrasound probe enhanced enzymatic hydrolysis for rapid separation of β2-adrenergic agonists from animal urine and livestock wastewater: Applicability to biomonitoring investigation - Zhiming Xiao; Yinji Jin; Ying Cao; Ting Yao; Yao Fu; Decheng Suo; Shi Wang; Gang Chen; Xinxue Zhao; Runxian Li; Xia Fan (Analytica Chimica Acta, 2024)

Garciyunnanones A–R: Caged polycyclic polyprenylated acylphloroglucinols decorated with a lavandulyl substituent from Garcinia yunnanensis - Miaomiao Nan; Yueyou Yang; Ping Ying; Qiang Zheng; Youjun Wu; Tianjie Cao; Ting Li; Weiming Huang; Chuanlu Fu; Lingyi Kong; Wenjun Xu (Phytochemistry, 2024)

Significantly accelerated aerobic granulation using Ca(ClO)2 hydrothermally pretreating sludge - Tingting Cao; Xiaomeng Li; Yue Yang; Xiaoqiu Xia; Leilei Zhang; Ying Lu; Dandan Zhou (Journal of Water Process Engineering, 2024)

Steep oceanic DIC δ13C depth gradient during the Hirnantian Glaciation - Shengchao Yang; Junxuan Fan; Thomas J. Algeo; Graham A. Shields; Ying Zhou; Chao Li; Jitao Chen; Weiqiang Li; Na Li; Jian Cao; Linna Zhang; Zongyuan Sun; et al. (Earth-Science Reviews, 2024)

A novel HMGA2/MPC-1/mTOR signaling pathway promotes cell growth via facilitating Cr (VI)-induced glycolysis - Siyang Zhao; Yahui Zhang; Shibo Bao; Liping Jiang; Qiujuan Li; Ying Kong; Jun Cao (Chemico-Biological Interactions, 2024)

Enhanced sludge granulation and stable performance of an anammox expanded granular sludge bed (EGSB) reactor through the utilization of hydroxyapatite (HAP) particles - Lan Lin; Ying Song; Yanlong Zhang; Zibin Luo; Qian Li; Wenzhi Cao; Yu-You Li (Bioresource Technology, 2024)

Metagenomic Next-Generation Sequencing as an Effective Diagnostic Tool for Talaromycosis in HIV-Negative Patients - Li Jiang; Tian-wei Liang; Najwa Al-Odaini; Yuan Hu; Minli Huang; Lili Wei; Xiu-ying Li; Kai-su Pan; Dong-yan Zheng; Zhi-wen Jiang; Gao Wei; Cun-wei Cao (Mycopathologia, 2024)

Repeat treatment of organotypic airway cultures with ethyl methanesulfonate causes accumulation of somatic cell mutations without expansion of bronchial-carcinoma-specific cancer driver mutations - Yiying Wang; Yuan Le; Kelly L. Harris; Ying Chen; Xilin Li; Jennifer Faske; Rebecca A. Wynne; Roberta A. Mittelstaedt; Xuefei Cao; Jaime Miranda-Colon; Lana Elkins; Levan Muskhelishvili; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Thawed drip and its membrane-separated components: Role in retarding myofibrillar protein gel deterioration during freezing-thawing cycles - Yang Li; Xiaoyu Han; Yuemei Zhang; Ying Wang; Jinpeng Wang; Wendi Teng; Wei Wang; Jinxuan Cao (Food Research International, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Engineering multifunctional phase change composites enabled by dual-interpenetrating hybrid scaffold for excellent thermal conductivity and electromagnetic absorption - Boyang Hu; Hong Guo; Ying Cui; Jiaye Li; Min Cao; Weiyan Qi; Xiwei Cao; Baoan Li (Chemical Engineering Journal, 2024)

Transport and risk of airborne pathogenic microorganisms in the process of decentralized sewage discharge and treatment - Yunping Han; Xuezheng Yu; Yingnan Cao; Jianguo Liu; Ying Wang; Zipeng Liu; Chenlei Lyu; Yilin Li; Xu Jin; Yuxiang Zhang; Yu Zhang (Water Research, 2024)

Research progress of industrial wastewater treatment technology based on solar interfacial adsorption coupled evaporation process - Juan Li; Yaowen Cao; Kuan Ding; Jianling Ye; Fenqiang Li; Chenbo Ma; Peihong Lv; Ying Xu; Lei Shi (Science of The Total Environment, 2024)

Triclocarban and triclosan promote breast cancer progression in vitro and in vivo via activating G protein-coupled estrogen receptor signaling pathways - Ting-Ting He; Xin Li; Jie-Zhi Ma; Yuan Yang; Shiye Zhu; Jianhua Zeng; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2024)

Dependence of evolution of Cyanobacteria superiority on temperature and nutrient use efficiency in a meso-eutrophic plateau lake - Jing Cao; Yue Wu; Ze-kun Li; Ze-ying Hou; Tian-hao Wu; Zhao-sheng Chu; Bing-hui Zheng; Ping-ping Yang; Yi-yan Yang; Cun-sheng Li; Qian-hua Li; Xia Guo (Science of The Total Environment, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Nervonic acid suppresses MPTP-induced Parkinson's disease in an adult zebrafish model by regulating the MAPK/NF-κB signaling pathway, inflammation, apoptosis, and oxidative stress - Xueqi Wang; Ying Mao; Tingyu Liang; Zhengdou Li; Xu Li; Xinliang Zhu; Fuliang Cao; Ji Zhang (Food Bioscience, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

The auxin response factor (ARF) gene family in Cyclocarya paliurus: genome-wide identification and their expression profiling under heat and drought stresses - Ziyong Gao; Yazhu Wu; Muzi Li; Lan Ding; Junyi Li; Ying Liu; Yu Cao; Yangguang Hua; Qiaojun Jia; Dekai Wang (Physiology and Molecular Biology of Plants, 2024)

The formation mechanism, analysis strategies and regulation measures of cereal aroma: A review - Yao Feng; Hongwei Cao; Hongdong Song; Kai Huang; Yu Zhang; Ying Zhang; Sen Li; Yingjie Li; Jun Lu; Xiao Guan (Trends in Food Science & Technology, 2024)

Observation of non-Hermitian skin effect in thermal diffusion - Yun-Kai Liu; Pei-Chao Cao; Minghong Qi; Qiang-Kai-Lai Huang; Feng Gao; Yu-Gui Peng; Ying Li; Xue-Feng Zhu (Science Bulletin, 2024)

Sublethal effect and detoxifying metabolism of metaflumizone and indoxacarb on the fall armyworm, Spodoptera frugiperda - Li Zhang; Hui-Zi Wu; Pei-Yun He; Hai-Qun Cao; Wan-Na Zhang; Ying-Chuan Peng; Cheng-Wang Sheng (Pesticide Biochemistry and Physiology, 2024)

Nonmetal catalyst boosting amplification of both colorimetric and electrochemical signal for multi-mode nitrite sensing - Ying Li; Yuyang Zhang; Rida Javed; Rui Li; Hongbin Zhao; Xing Liu; Chenghui Zhang; Hongmei Cao; Daixin Ye (Food Chemistry, 2024)

Stability and gastrointestinal behavior of curcumin-loaded emulsion stabilized by multi-conformation soy proteins: Influence of oil volume fraction - Jiayan Lu; Ying Wang; Wenhui Cao; Yan Yan; Fengxian Guo; Jianlin Li; Weiwei Li (Food Chemistry, 2024)

Ball-milled sepiolite/phosphate rock for simultaneous remediation of cadmium-contaminated farmland and alleviation of phosphorus deficiency symptoms in pepper - Jianhua Qu; Yuhui Li; Hebang Sun; Ruixin Liu; Yue Han; Fuxuan Bi; Hongli Fan; Guosheng Zhang; Yupeng Zhang; Yifan Wang; Weidong Cao; Ying Zhang (Chemical Engineering Journal, 2024)

Superabsorbent carboxymethyl cellulose–based hydrogel fabricated by liquid-metal-induced double crosslinking polymerisation - Qi Cao; Jing Chen; Miao Wang; Zhigang Wang; Wenjun Wang; Yanqin Shen; Ying Xue; Bo Li; Yanli Ma; Yijun Yao; Hailiang Wu (Carbohydrate Polymers, 2024)

Inhibition of human UDP-glucuronosyltransferase enzyme by entrectinib: Implications for drug-drug interactions - Hang Yin; Zhe Wang; Xin Lv; Zhen Wang; Ying Wang; Wenxuan Fan; Shuang Li; Lili Jiang; Jun Cao; Yong Liu (Chemico-Biological Interactions, 2024)

Apigenin delays postovulatory oocyte aging by reducing oxidative stress through SIRT1 upregulation - Xuerui Yao; Panpan Guo; Ying-Hua Li; Hao Guo; Zhelong Jin; Wen Lui; Jianbin Yuan; Qingshan Gao; Lin Wang; Yunxiao Li; Jiabin Shi; Xiwei Zhang; et al. (Theriogenology, 2024)

Response of late Holocene vegetation to abrupt climatic events on the northwestern coast of the Bay of Bohai, China - Rongrong Wang; Yuecong Li; Shengrui Zhang; Qinghai Xu; Yawen Ge; Bing Li; Baoshuo Fan; Zhen Zhang; Cange Li; Ying Wang; Hanfei You; Yihang Cao; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Co-foliar application of zinc and nano-silicon to rice helps in reducing cadmium exposure risk: Investigations through in-vitro digestion with human cell line bioavailability assay - Qiang Lin; Yasir Hamid; Honhang Wang; Min Lu; Xuerui Cao; Tong Zou; Zhiqin Chen; Bilal Hussain; Ying Feng; Tingqiang Li; Zhenli He; Xiaoe Yang (Journal of Hazardous Materials, 2024)

Deep recycling of crustal materials by the Hainan mantle plume: evidence from Zn–Sr–Nd–Pb isotopes of Hainan Island basalts - Guangyue Cao; Ying Tong; Xianchun Tang; Xiangdong Wang; Xiang Li; Lei Wang (Contributions to Mineralogy and Petrology, 2024)

Mechanical performance of CRTS II slab tracks in reinforced-unreinforced transition zone in extreme heat events - Yang Li; Haiyan Li; Rui Zhou; Jinjie Chen; Ying Song; Kailin Cao (Transportation Geotechnics, 2024)

Knockdown of TXNIP alleviates gestational diabetes mellitus by activating autophagy to regulate cell proliferation and apoptosis in high glucose-treated trophoblasts - Ying Gu; Minkai Cao; Yu Chen; Jingyang Li; Lingli Hu; Xiao-Jun Yang (Reproductive Biology, 2024)

Contrasting response strategies of sulfate-reducing bacteria in a microbial consortium to As3+ stress under anaerobic and aerobic environments - Miaomiao Li; Jun Yao; Yating Wang; Geoffrey Sunahara; Robert Duran; Jianli Liu; Bang Liu; Houquan Liu; Bo Ma; Hao Li; Wancheng Pang; Ying Cao (Journal of Hazardous Materials, 2024)

Analysis of key enzyme activity and aroma volatile compounds in microwave-irradiated quinoa during storage - Hongwei Cao; Jinzhe Han; Rulian Sun; Zhaoxia Li; Yu Zhang; Hongdong Song; Kai Huang; Ying Zhang; Xiao Guan (Journal of Cereal Science, 2024)

Eco-friendly management of Meloidogyne incognita in cadmium-contaminated soil by using nematophagous fungus Purpureocillium lavendulum YMF1.683: Efficacy and mechanism - Xin Li; Lian-Ming Liang; Zhi-Bin Hua; Xin-Kui Zhou; Ying Huang; Jin-Hua Zhou; Yi Cao; Jian-Jin Liu; Tong Liu; Ming-He Mo (Environmental Research, 2024)

Degradation of typical flotation reagents using lead-zinc smelting slag as mediator for persulfate activation: Effect of gallic acid and Cr(VI) on the removal performance and fate of reactive oxygen species - Wancheng Pang; Jun Yao; Tatjana Šolević Knudsen; Ying Cao; Bo Ma; Hao Li; Miaomiao Li; Bang Liu (Environmental Pollution, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Identification of a novel adenovirus in liver tissue sample of the Great Himalayan leaf-nosed bat (Hipposideros armiger) - Ling Cao; Xulai Song; Yu Qian; Ying Li; Jian Xu; Xurong Chen; Xiaochun Wang; Jianguo Chen (Brazilian Journal of Microbiology, 2024)

Growth arrest and DNA damage-inducible 45 ab gene targeted by miR-20b-5p executes the inflammation and apoptosis by regulating MAPK and NF-κB pathways in black rockfish - Chengbin Gao; Peng Sun; Xin Cai; Le Ma; Ying Zhu; Min Cao; Chao Li (Aquaculture, 2024)

Size-dependent influences of nanoplastics on microbial consortium differentially inhibiting 2, 4-dichlorophenol biodegradation - Ying Zhai; Wenbo Guo; Deping Li; Bo Chen; Xiaoyun Xu; Xinde Cao; Ling Zhao (Water Research, 2024)

The synergistic effect of oxidant-peroxide coupling systems for water and wastewater treatments - Ying Cao; Juan Li; Zhen Wang; Chaoting Guan; Jin Jiang (Water Research, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

Enhanced and accelerated degradation of PFOA using visible light—Applying semiconductor carbon nitride as an accelerator - Juying Li; Ying Liu; Yiqian Song; Li Cao; Yezhi Dou; Jia Yu; Yueqing Zhang; Jian He; Wei Dai; Cheng Yao; Deyang Kong (Journal of Environmental Chemical Engineering, 2024)

Direct conversion of carbon dioxide into light olefins over ZnZrOx/ZSM-5@n-ZrO2 tandem catalyst - Ying Wang; Shike Liu; Jiamin Wang; Fei Liu; Jun Ma; Mengqin Yao; Shuo Geng; Jianxin Cao; Ziwei Li (Fuel, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Dry reforming of methane by La2NiO4 perovskite oxide: B-site substitution improving reactivity and stability - Dingshan Cao; Cong Luo; Tong Luo; Zhaowei Shi; Fan Wu; Xiaoshan Li; Ying Zheng; Liqi Zhang (Chemical Engineering Journal, 2024)

Hydrogel coatings on universal medical devices with water-responsive Janus adhesion and acidity-triggered transformation for adaptive antibacterial treatment and fluorescence diagnosis - Yanyun Liu; Ming Li; Ying Zheng; Changhua Liu; Yang Cao; Wei Guo; Ming Liu; Jiaqi Qian; Chenchi Gong; Xueqin Shuang; Gaoxing Pan; Wei Huang; et al. (Chemical Engineering Journal, 2024)

Xylan cinnamoylation for reinforcing poly (butylene adipate-co-terephthalate): Molecule design and interaction optimization - Yanjun Chen; Jie Dai; Xin Shen; Junqiang Shan; Yulian Cao; Tianpeng Chen; Hanjie Ying; Chenjie Zhu; Ming Li (Carbohydrate Polymers, 2024)

Effects of Brown Fishmeal on Growth Performance, Digestibility, and Lipid Metabolism of the Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Guo-Fang Zhong; Liang-Fa Zhang; Yi Zhuang; Qi Li; He Huang; Cong Cao; Zhan-Ying Zhu; Zhong-Yuan Huang; Nu-An Wang; Kun Yuan (Marine Biotechnology, 2024)

Effects of tillage practices on soil organic carbon, microbial community and necromass in a double rice cropping system - Jian-Ying Qi; Xiang-Bin Yao; Xue-Chan Zhang; Mei-Yi Fan; Jian-Fu Xue; Jun-Li Cao; Ahmad Latif Virk; Sheng-Gang Pan; Xiang-Ru Tang (Applied Soil Ecology, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Climate and sea-level fluctuations on the western coast of Bohai Bay during the 4.2 ka event: Multi-proxy evidence from the Nandagang area of Cangzhou, China - Hanfei You; Yuecong Li; Shengrui Zhang; Yawen Ge; Zhen Zhang; Wensheng Zhang; Ying Wang; Baoshuo Fan; Rongrong Wang; Yihang Cao; Cange Li (Quaternary Science Reviews, 2024)

Petrogenesis of magnesian troctolitic granulite clasts from Chang'e -5 drilling sample: Implications for the origin of ejecta material from lunar highlands - Qi He; Zhi Cao; Yuqi Qian; Hejiu Hui; Ioannis Baziotis; Long Xiao; Zaicong Wang; Biji Luo; Yiheng Li; Zongjun Ying; Yang Li (Icarus, 2024)

Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2024)

Synergistic effect between Ni single atoms and Ni nanoparticles for effectively boosting sustainable co-electrolysis of CO2 and hydrazine - Min Li; Ye Hu; Wenhui Fang; Shixian Xin; Ying Wu; Yutao Cao; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Low temperature relaxor, polarization dynamics and energy storage properties of Ca0.28Ba0.72Nb2O6 tungsten bronze ceramics - Lei Cao; Yuanyuan Wang; Ying Yuan; Jianguo Zhu; Hadi Barzegar Bafrooei; Minmin Mao; Bing Liu; Hao Li; Dawei Wang; Zhilun Lu; Ge Wang; Kaixin Song (Chemical Engineering Journal, 2024)

Systematic metabolic engineering of Yarrowia lipolytica for the enhanced production of erythritol - Shuling Yang; Xuewei Pan; Jiajia You; Baomin Guo; Zuyi Liu; Ying Cao; Guomin Li; Minglong Shao; Xian Zhang; Zhiming Rao (Bioresource Technology, 2024)

MiRNA320a Inhibitor-Loaded PLGA-PLL-PEG Nanoparticles Contribute to Bone Regeneration in Trauma-Induced Osteonecrosis Model of the Femoral Head - Ying Zhang; Chuan Li; Qiushi Wei; Qiang Yuan; Wei He; Ning Zhang; Yiping Dong; Zhenhao Jing; Leilei Zhang; Haibin Wang; Xiangyang Cao (Tissue Engineering and Regenerative Medicine, 2024)

Changes in years of life lost and life expectancy by reducing air pollution - Ying Liu; Shuxia Yang; Chunyu Li; Qidi Fang; Chuang Han; Chuanlong Cheng; Yunxian Cao; Feng Cui; Xiujun Li (Air Quality, Atmosphere & Health, 2024)

Diarylpentanoids and phenylpropanoids from the roots of Anthriscus sylvestris (L.) Hoffm - Yan-ling Liu; Yan-gang Cao; Ying Niu; Ya-juan Zheng; Xu Chen; Ying-jie Ren; Xi-ling Fan; Xiang-da Li; Xin-yi Ma; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2023)

Research advances of molecular docking and molecular dynamic simulation in recognizing interaction between muscle proteins and exogenous additives - Genpeng Bai; Yiling Pan; Yuemei Zhang; Yang Li; Jinpeng Wang; Ying Wang; Wendi Teng; Guofeng Jin; Fang Geng; Jinxuan Cao (Food Chemistry, 2023)

Blood Transcriptome Analysis Provides Responsive Changes in Gene Expression between Ex Situ and Captive Yangtze Finless Porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Zhichen Cao; Denghua Yin; Zhanwei Li; Yan Yan; Peng Zhang; Sigang Zhang; Danqing Lin; Zhong Hua; Jialu Zhang; Congping Ying; Han Zhang; Pao Xu; et al. (Fishes, 2023)
The Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis, YFP) is an endangered species endemic to the Yangtze River in China, and it is the only freshwater whale in the genus Neophocaena. In terms of protection, three effective conservation strategies exist: in situ conservation, ex situ conservation, and artificial breeding, all of which have been implemented by the Chinese government. Of these, ex situ conservation involves the relocation of Yangtze finless porpoises to semi-natural waters with less human interference, and artificial breeding involves the relocation of Yangtze finless porpoises to a controlled environment that is more strictly managed. To compare and analyze the responsive changes in gene expression of the YFPs between the ex situ and controlled environments, we performed the RNA sequencing of blood tissues from these YFPs. A total of 1201 differentially expressed genes (DEGs) were identified, of which 423 were up-regulated in the ex situ population and 778 were up-regulated in the controlled-environment population. Gene enrichment analysis showed that 1201 DEGs between the ex situ and controlled-environment populations were generally enriched for vision-, digestion- and immune-system-related pathways. Further analysis revealed that several key immune system pathways, such as the chemokine signaling pathway and B cell receptor signal pathway, were activated in the ex situ population. In addition, the key pathways related to vision, including phototransduction and the inflammatory mediator regulation of TRP channels, as well as the pathways related to the digestive system, such as protein digestion and absorption and salivary secretion, were activated in the controlled-environment population. These results suggest that the ex situ populations may respond to complex environmental conditions in semi-natural waters by enhancing their immune function through the increased expression of immune-related genes and that the visual function and protein digestion of the YFPs were improved compared to those of the ex situ population based on the conditions of artificial feeding, such as the higher transparency of the water and regular feeding. This study provides clues for evaluating the adaptability of YFPs to different environments and is a useful reference for future ex situ conservation and artificial breeding.

Shifting of nutrient limitation dominates the recovery of aboveground net primary productivity of mixed forests in northeastern China after selective logging - Zhaopeng Song; Hongyan Liu; Jihua Hou; Yanhong Liu; Ying Li; Liang Shi; Jing Cao (Science of The Total Environment, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

Synergy between fayalite-constituted waste copper smelting slag and hydroxylamine: An efficient combination for construction and application of a surface Fenton system in removal of mining organic pollutants - Ying Cao; Jun Yao; Tatjana Šolević Knudsen; Wancheng Pang; Bo Ma; Hao Li; Chenchen Zhao; Bang Liu; Miaomiao Li (Journal of Cleaner Production, 2023)

Spatiotemporal dynamics of phytoplankton biomass and community succession for driving factors in a meso-eutrophic lake - Jing Cao; Ze-ying Hou; Ze-kun Li; Bing-hui Zheng; Zhao-sheng Chu (Journal of Environmental Management, 2023)

Step-feeding food waste fermentation liquid as supplementary carbon source for low C/N municipal wastewater treatment: Bench scale performance and response of microbial community - Zhenjun Tian; Guowen Li; Ying Xiong; Xiaoxin Cao; Hongtao Pang; Wenzhong Tang; Yongli Liu; Miaoxin Bai; Qiuheng Zhu; Caili Du; Maotong Li; Lieyu Zhang (Journal of Environmental Management, 2023)

The aggregated biofilm dominated by Delftia tsuruhatensis enhances the removal efficiency of 2,4-dichlorophenol in a bioelectrochemical system - Deping Li; Wenbo Guo; Ying Zhai; Xiaoyun Xu; Xinde Cao; Ling Zhao (Environmental Pollution, 2023)

Genetic Architecture and Functional Implications of the CSF-Contacting Nucleus - Siyuan Song; Yumin Yuan; Lingling Xu; Jun Jiang; Ying Li; Yao Yan; Qing Li; Fang Zhou; Junli Cao; Licai Zhang (Neuroscience Bulletin, 2023)
We previously identified a unique nucleus, the cerebrospinal fluid (CSF)-contacting nucleus. This study aims to understand its gene architecture and preliminarily suggest its functions. The results showed that there were about 19,666 genes in this nucleus, of which 913 were distinct from the dorsal raphe nucleus (non-CSF contacting). The top 40 highly-expressed genes are mainly related to energy metabolism, protein synthesis, transport, secretion, and hydrolysis. The main neurotransmitter is 5-HT. The receptors of 5-HT and GABA are abundant. The channels for Cl – , Na + , K + , and Ca 2+ are routinely expressed. The signaling molecules associated with the CaMK, JAK, and MAPK pathways were identified accurately. In particular, the channels of transient receptor potential associated with nociceptors and the solute carrier superfamily members associated with cell membrane transport were significantly expressed. The relationship between the main genes of the nucleus and life activities is preliminarily verified.

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Microbial metabolic activity in metal(loid)s contaminated sites impacted by different non-ferrous metal activities - Hao Li; Jun Yao; Ning Min; Geoffrey Sunahara; Jianli Liu; Miaomaio Li; Bang Liu; Wancheng Pang; Ying Cao; Ruofei Li; Robert Duran (Journal of Hazardous Materials, 2023)

Carbon deposition properties and regeneration performance of La2NiO4 perovskite oxide for dry reforming of methane - Dingshan Cao; Cong Luo; Zengqiang Tan; Tong Luo; Zhaowei Shi; Fan Wu; Xiaoshan Li; Ying Zheng; Liqi Zhang (Journal of Environmental Chemical Engineering, 2023)

Estimation of canopy water content for wheat through combining radiative transfer model and machine learning - Jie Zhu; Jingshan Lu; Wei Li; Ying Wang; Jiale Jiang; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao (Field Crops Research, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Vardenafil alleviates cigarette smoke-induced chronic obstructive pulmonary disease by activating autophagy via the AMPK/mTOR signalling pathway: an in vitro and in vivo study - Weihao Li; Jingxia Yan; Jing Xu; Liqin Zhu; Cuijuan Zhai; Yajuan Wang; Yuxin Wang; Ying Feng; Huifang Cao (In Vitro Cellular & Developmental Biology - Animal, 2023)

Study on the planning and influential factors of the safe width of riparian buffer zones in the upper and middle reaches of the Ziwu River, China - Hang Chen; Xiaode Zhou; Ying Wang; Wei Wu; Li Cao; Xin Zhang (Environmental Science and Pollution Research, 2023)

Genetic diversity, antibiotic resistance, and virulence characteristics of Staphylococcus aureus from raw milk over 10 years in Shanghai - Jiewen Huang; Wengang Zhang; Bingqing Sun; Qin Jiang; Ying Cao; Jun Shang; Yu Zhang; Xin Gu; Chao Lv; Chaoyi Guo; Min Li; Hui Li; et al. (International Journal of Food Microbiology, 2023)

Electronic modulation and surface reconstruction on heterostructured CoP-Ni2P nanosheets with phosphate-rich surface for synergistically triggering oxygen evolution reaction - Fei Nie; Xueli Yin; Yihua Cao; Zhi Li; Xiaoping Dai; Weiyu Song; Yujie Liu; Yonghao Gan; Ying Ye; Run Cai; Xin Zhang (Fuel, 2023)

Fine lithospheric structure controlling Meso-Cenozoic tectono-magmatism in the South China Block: Inference from a multidisciplinary analysis - Feiyu Zhao; Yanhui Suo; Lijun Liu; Xianzhi Cao; Sanzhong Li; Suhua Jiang; Juzhi Deng; Mengxue Dai; Ying Liu; Yaping Hu; Shuzhong Sheng; Bin Hu (Earth-Science Reviews, 2023)

Overexpression of Taetr1-1 promotes enhanced seed dormancy and ethylene insensitivity in wheat - Jun Wei; Xing-ting Wu; Xiao-ying Li; Wim J. J. Soppe; Hong Cao; Yong-xiu Liu (Planta, 2023)

T-2 toxin-induced chondrocyte apoptosis contributes to growth plate damage through Smad2 and Smad3 signaling - Ying He; Yawen Shi; Ying Zhang; Ruotong Zhang; Li Cao; Yinan Liu; Tianyou Ma; Jinghong Chen (Toxicon, 2023)

A new insight into the CaO-induced inhibition pathways on PCDD/F formation: Metal passivation, dechlorination and hydroxide substitution - Xiaoxiao Wang; Jiabao Lv; Yuxuan Ying; Yunfeng Ma; Angjian Wu; Xiaoqing Lin; Ang Cao; Xiaodong Li; Jianhua Yan (Science of The Total Environment, 2023)

Nanographite-assisted matrix solid phase dispersion microextraction of active and toxic compounds from complex food matrices using cyclodextrin aqueous solution as elution solvent - Si-Chen Zhu; Ying Shi; Huang-Fei Jin; Jun Cao; Li-Hong Ye (Food Chemistry, 2023)

Schiff base type casein-konjac glucomannan conjugates with improved stability and emulsifying properties via mild covalent cross-linking - Ying Kuang; Si Zhao; Puming Liu; Menglong Liu; Kao Wu; Yi Liu; Pengpeng Deng; Cao Li; Fatang Jiang (Food Hydrocolloids, 2023)

Tartary buckwheat-derived exosome-like nanovesicles against starch digestion and their interaction mechanism - Dan Li; Guifang Cao; Xiaolin Yao; Yongli Yang; Dan Yang; Ning Liu; Ying Yuan; Katsuyoshi Nishinari; Xi Yang (Food Hydrocolloids, 2023)

Layered B2O3/CsPbBr3 perovskite composite embedded using glass as microreactor with enhanced stability and high-efficiency light extraction - Ying Liu; Shuai Yang; Xiaobo Luo; Zhangwen Long; Enhao Cao; Junhao Li; Yan Chen; Qi Wang; Yong Yang; Chunjian Wang; Yuan Gao; Jianbei Qiu; et al. (Chemical Engineering Journal, 2023)

Evaluation of Physiological Stress of Grass Carp Chronically Exposed to Enrofloxacin Based on IBR Index - Xu-Qian Cao; Xu Wang; Bin Liu; Shu-Wen He; Zhi-Han Cao; Shao-Ying Xing; Ping Li; Zhi-Hua Li (Water, Air, & Soil Pollution, 2023)

Sphk1 deficiency induces apoptosis and developmental defects and premature death in zebrafish - Ling Huang; Fang Han; Ying Huang; Jieping Liu; Xinjun Liao; Zigang Cao; Wanbo Li (Fish Physiology and Biochemistry, 2023)

In-situ detection equipment for radon-in-water: unattended operation and monthly investigations - Chunqian Li; Meng Li; Guangquan Chen; Huaming Yu; Chenglun Zhang; Wen Liu; Jinjia Guo; Shibin Zhao; Lijun Song; Xiliang Cui; Ying Chai; Lu Cao; et al. (Acta Oceanologica Sinica, 2023)

Performance of Zeolite and Trace Elements on Biogas Production from Alkaline Hydrogen Peroxide–Pretreated Sweet Sorghum Bagasse Slurry - Xuemei Li; Ying Xiao; Rui Zhang; Chen Sun; Weixing Cao (BioEnergy Research, 2023)

Protective effect of chicken egg yolk immunoglobulin (IgY) against Spiroplasma eriocheiris infection in Chinese mitten crab - Ying Guo; Yubo Ma; Hendriansyah Endri; Yanlan Huang; Xinyu Pan; Suyue Qiu; Yawei Cao; Wei Gu; Jie Du; Li Wang; Qingguo Meng (Aquaculture, 2023)

CpG ODN 1668 as TLR9 agonist mediates humpback grouper (Cromileptes altivelis) antibacterial immune responses - Xiaojuan Chen; Panpan Zhang; Pengshuo Li; Guotao Wang; Jianlong Li; Ying Wu; Zhenjie Cao; Yongcan Zhou; Yun Sun (Fish & Shellfish Immunology, 2023)

Integrating polygenic and clinical risks to improve stroke risk stratification in prospective Chinese cohorts - Qingmei Cui; Fangchao Liu; Jianxin Li; Xiaoge Niu; Zhongying Liu; Chong Shen; Dongsheng Hu; Keyong Huang; Shufeng Chen; Jie Cao; Xiaoqing Liu; Ling Yu; et al. (Science China Life Sciences, 2023)

Tracing the future of epidemics: Coincident niche distribution of host animals and disease incidence revealed climate‐correlated risk shifts of main zoonotic diseases in China - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Yiyang Su; Lingyu Che; Meng Zhang; Yumeng Lu; Pufan Gao; Jingjing Yang; Ying Xue; Guishuang Li (Global Change Biology, 2023)
Climate has critical roles in the origin, pathogenesis and transmission of infectious zoonotic diseases. However, large‐scale epidemiologic trend and specific response pattern of zoonotic diseases under future climate scenarios are poorly understood. Here, we projected the distribution shifts of transmission risks of main zoonotic diseases under climate change in China. First, we shaped the global habitat distribution of main host animals for three representative zoonotic diseases (2, 6, and 12 hosts for dengue, hemorrhagic fever, and plague, respectively) with 253,049 occurrence records using maximum entropy (Maxent) modeling. Meanwhile, we predicted the risk distribution of the above three diseases with 197,098 disease incidence records from 2004 to 2017 in China using an integrated Maxent modeling approach. The comparative analysis showed that there exist highly coincident niche distributions between habitat distribution of hosts and risk distribution of diseases, indicating that the integrated Maxent modeling is accurate and effective for predicting the potential risk of zoonotic diseases. On this basis, we further projected the current and future transmission risks of 11 main zoonotic diseases under four representative concentration pathways (RCPs) (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) in 2050 and 2070 in China using the above integrated Maxent modeling with 1,001,416 disease incidence records. We found that Central China, Southeast China, and South China are concentrated regions with high transmission risks for main zoonotic diseases. More specifically, zoonotic diseases had diverse shift patterns of transmission risks including increase, decrease, and unstable. Further correlation analysis indicated that these patterns of shifts were highly correlated with global warming and precipitation increase. Our results revealed how specific zoonotic diseases respond in a changing climate, thereby calling for effective administration and prevention strategies. Furthermore, these results will shed light on guiding future epidemiologic prediction of emerging infectious diseases under global climate change.

Environmental heterogeneity affecting spatial distribution of phytoplankton community structure and functional groups in a large eutrophic lake, Lake Chaohu, China - Huijuan Cao; Kun Zhang; Daogui Deng; Huiying Qi; Jun Li; Yaqin Cao; Qide Jin; Yajie Zhao; Yeping Wang; Zhou Wu; Xinyue Li; Ying Li (Environmental Science and Pollution Research, 2023)
The growth and development of phytoplankton are influenced by physico-chemical parameters, which can also affect the spatial distribution of phytoplankton community structure. However, it is unclear whether environmental heterogeneity caused by multiple physico-chemical factors can affect the spatial distribution of phytoplankton and its functional groups. In this study, we investigated the seasonal variation and spatial distribution of phytoplankton community structure and its relationships with environmental factors in Lake Chaohu from August 2020 to July 2021. We recorded a total of 190 species from 8 phyla, which were divided into 30 functional groups, including 13 dominating functional groups. The average annual phytoplankton density and biomass were (5.46 ± 7.17) × 10 7 cells/L and 4.80 ± 4.61 mg/L, respectively. The density and biomass of phytoplankton were higher in summer ((14.64 ± 20.34) × 10 7 cells/L, 10.61 ± 13.16 mg/L) and autumn ((6.79 ± 3.97) × 10 7 cells/L, 5.57 ± 2.40 mg/L), with the M and H2 of dominant functional groups. The dominant functional groups were N, C, D, J, MP, H2, and M in spring, whereas functional groups C, N, T, and Y dominated in winter. The distribution of phytoplankton community structure and dominant functional groups exhibited significant spatial heterogeneity in the lake, which was consistent with the environmental heterogeneity of the lake and could be classified into four locations. Location I had higher phytoplankton density and biomass than the other three locations. Additionally, dominant functional groups M, C, and H2 were present throughout the lake, and all 13 dominant functional groups were observed in Location II. Our findings suggest that environmental heterogeneity is a key factor influencing the spatial distribution of phytoplankton functional groups in Lake Chaohu.

One global disseminated 193 kb high-risk hybrid plasmid harboring tet(X4), mcr or blaNDM threatening public health - Min Li; Haoran Zhang; Wengang Zhang; Ying Cao; Bingqing Sun; Qin Jiang; Yu Zhang; Haodong Liu; WenNan Guo; Cheng Chang; Nan Zhou; Chao Lv; et al. (Science of The Total Environment, 2023)

The BrAFP1 promoter drives gene-specific expression in leaves and stems of winter rapeseed (Brassica rapa L.) under cold induction - Xiaoyun Dong; Zigang Liu; Jiaping Wei; Guoqiang Zheng; Hui Li; Ying Wang; Haiyan Tian; Junmei Cui; Zefeng Wu; Xiaodong Cao; Chunmei Xu (Plant Science, 2023)

Assembly processes of bacterial and fungal communities in metal(loid)s smelter soil - Miaomiao Li; Jun Yao; Geoffrey Sunahara; Robert Duran; Bang Liu; Ying Cao; Hao Li; Wancheng Pang; Houquan Liu; Shun Jiang; Junjie Zhu; Qinghua Zhang (Journal of Hazardous Materials, 2023)

Degradation of metoprolol by UV/sulfite as an advanced oxidation or reduction process: The significant role of oxygen - Ying Cao; Juan Li; Yanxin Zhao; Yumeng Zhao; Wei Qiu; Suyan Pang; Jin Jiang (Journal of Environmental Sciences, 2023)

Salinity variations of the inner Yangtze Sea during the Ordovician-Silurian transition and its influences on marginal marine euxinia - Guangyao Cao; Yu Liu; Chao Li; Ping'an Peng; Mingcai Hou; Gary G. Lash; Xiaolin Zhou; Yuanchun Li; Ying Song (Global and Planetary Change, 2023)

In-situ constructing nano ternary Ni-P-Cu alloy shell on the micro-aluminum surface: Enhancing its ignition and combustion performances - Chao Wang; Ying Liu; Kang Niu; Jia Li; Qing Cao; Xiuchen Zhao; Hongyang Li; Ningfei Wang; Baolu Shi (Fuel, 2023)

CpG ODN 2102 promotes antibacterial immune responses and enhances vaccine-induced protection in golden pompano (Trachinotus ovatus) - Xiaojuan Chen; Ying Wu; Yulin Qiu; Pengshuo Li; Zhenjie Cao; Yongcan Zhou; Yun Sun (Fish & Shellfish Immunology, 2023)

Targeting of platinum capture under 1+1 aqua regia using robust and recyclable polymeric polyamine resin: Adsorption performance and mechanism - Bohan Li; Wei Xiong; Ying Cao; Xiaoyu Zhou; Haochen Zhu; Min Li; Liming Yang; Penghui Shao (Environmental Research, 2023)

Engineering brain-derived neurotrophic factor mRNA delivery for the treatment of Alzheimer’s disease - Haoyuan Li; Yan Cao; Jingjing Ye; Zhipeng Yang; Qimingxing Chen; Xiaoqin Liu; Bohan Zhang; Jingwen Qiao; Qisheng Tang; Huiying Yang; Jianfeng Li; Zhifeng Shi; et al. (Chemical Engineering Journal, 2023)

Effects of kaolin particle film coatings on the water-saving efficiency and fruit quality of Cabernet Sauvignon (Vitis vinifera L.) grape plants in the Ningxia region of China - Xiao Cao; Ying Wang; Zhi-Lei Wang; Xue-Lin Tian; Xing Han; Dong Wu; Fei Yao; Miao Hui; Hua Li; Hua Wang (Horticulture, Environment, and Biotechnology, 2023)

Reversal of H2O2-induced cell death by knockdown of HOTAIR in HTR-8/SVneo cells by mediation of miR-106b-5p/ACSL4 axis - Minkai Cao; Weilai Jin; Ying Li; Mingxin Wang; Faguang Wan; Yongwei Ren; Ying Gu; Jinqi Ma; Le Zhang (Functional & Integrative Genomics, 2023)

Distributed spatial crowdsourcing based task allocation in Ocean Internet of Things - Hongtang Cao; Ying Guo; Fei Li; Keyi Zhang (Earth Science Informatics, 2023)

PM2.5 caused ferroptosis in spermatocyte via overloading iron and disrupting redox homeostasis - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Ying Tang; Chang Liu; Yimeng Wang; Jianping Chen; Xiao Jiang; Huan Yang; Lei Sun; Qing Chen; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Quick and high-throughput quantification of 22 β-agonists residues in animal-derived foods using enzymatic probe sonication - Zhiming Xiao; Jun Wang; Ying Cao; Ting Yao; Shi Wang; Jia Liu; Decheng Suo; Jing Tian; Zheng Jia; Yang Li; Xia Fan (Food Chemistry, 2023)

Identifying the airport as a key urban VOC source in the Pearl River Delta, China - Bo Zhu; Li-Ming Cao; Shi-Yong Xia; Ying-Bo Niu; Han-Yang Man; Ke Du; Kuangyou Yu; Xiao-Feng Huang (Atmospheric Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Novel function of a putative TaCOBL ortholog associated with cold response - Fang-Fang Liu; Ying-Xiu Wan; Wen-Xin Cao; Qi-Qi Zhang; Yao Li; Yan Li; Ping-Zhi Zhang; Hong-Qi Si (Molecular Biology Reports, 2023)

Insights into the nitroaromatic compounds, formation, and light absorption contributing emissions from various geological maturity coals - Shasha Huang; Xueting Yang; Hongmei Xu; Yaling Zeng; Dan Li; Jian Sun; Steven Sai Hang Ho; Ying Zhang; Junji Cao; Zhenxing Shen (Science of The Total Environment, 2023)

Insights on nitrogen and phosphorus removal mechanism in a single-stage Membrane Aeration Biofilm Reactor (MABR) dominated by denitrifying phosphorus removal coupled with anaerobic/aerobic denitrification - Ming Li; Xiwei Cao; Ziqing Wu; Jiaye Li; Ying Cui; Jun Liu; Baoan Li (Journal of Water Process Engineering, 2023)

A colorimetric smartphone-based sensor for on-site AA detection in tropical fruits using Fe-P/N C single-atom nanoenzyme - Ying Li; Rida Javed; Rui Li; Yuyang Zhang; Ziyue Lang; Hongbin Zhao; Xing Liu; Hongmei Cao; Daixin Ye (Food Chemistry, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

The potential environmental risk implications of two typical non-ferrous metal smelting slags: contrasting toxic metal(loid)s leaching behavior and geochemical characteristics - Dongyang Men; Jun Yao; Hao Li; Gyozo Jordan; Baojin Zhao; Ying Cao; Bo Ma; Bang Liu; Yuanyuan Sun; Jiaxing Ban (Journal of Soils and Sediments, 2023)

Performance and mechanisms for Cd(II) and As(III) simultaneous adsorption by goethite-loaded montmorillonite in aqueous solution and soil - Chenchen Zhao; Jun Yao; Tatjana Šolević Knudsen; Jianli Liu; Xiaozhe Zhu; Bo Ma; Hao Li; Ying Cao; Bang Liu (Journal of Environmental Management, 2023)

Inhibition of ATF4-mediated elevation of both autophagy and AKT/mTOR was involved in antitumorigenic activity of curcumin - Jie Yang; Hasenbilige; Shibo Bao; Shengxiang Luo; Liping Jiang; Qiujuan Li; Ying Kong; Jun Cao (Food and Chemical Toxicology, 2023)

Potential of crop straw incorporation for replacing chemical fertilizer and reducing nutrient loss in Sichuan Province, China - Ying Wang; Bang-qiang Liang; Hui Bao; Qian Chen; Ya-lei Cao; Yan-qing He; Liang-zhong Li (Environmental Pollution, 2023)

Structural characterization and anti-inflammatory effects of an arabinan isolated from Rehmannia glutinosa Libosch. - Han Zhang; Yimin Yue; Qian Zhang; Lanyuan Liang; Chuanqiu Li; Ying Chen; Wei Li; Mingming Peng; Mengru Yang; Mantong Zhao; Xia Cao; Luyang Zhong; et al. (Carbohydrate Polymers, 2023)

Occurrence and spatial distribution of paralytic shellfish toxins in seawater and marine organisms in the coastal waters of Qinhuangdao, China - Yadong Cao; Jiangbing Qiu; Aifeng Li; Lei Zhang; Guowang Yan; Ying Ji; Jingrui Zhang; Peng Zhao; Xizhen Wu (Chemosphere, 2023)

Noval bio-organic fertilizer containing Arthrobacter sp. DNS10 alleviates atrazine-induced growth inhibition on soybean by improving atrazine removal and nitrogen accumulation - Zhao Jiang; Qi Shao; Yu Li; Bo Cao; Jin Li; Zheyi Ren; Jianhua Qu; Ying Zhang (Chemosphere, 2023)

Assessing the ecotoxicity of combined exposure to triphenyltin and norfloxacin at environmental levels: A case study of immunotoxicity and metabolic regulation in carp (Cyprinus carpio) - Si-Qi Zhang; Ping Li; Shu-Wen He; Shao-Ying Xing; Zhi-Han Cao; Xue-Li Zhao; Cuici Sun; Zhi-Hua Li (Chemosphere, 2023)

Autophagy induces mTOR-dependent glucose uptake and mTOR-independent lactate utilization in cadmium-treated A549 cells - Shibo Bao; Cong Zhang; Shengxiang Luo; Liping Jiang; Qiujuan Li; Ying Kong; Jun Cao (Toxicology in Vitro, 2023)

Characterizing formation mechanisms of secondary aerosols on black carbon in a megacity in South China - Jing Wei; Ying-Bo Niu; Meng-Xue Tang; Yan Peng; Li-Ming Cao; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Oxidative treatment of NOM by selective oxidants in drinking water treatment and its impact on DBP formation in postchlorination - Juan Li; Yang Song; Jin Jiang; Tao Yang; Ying Cao (Science of The Total Environment, 2023)

Four new Myrioneuron alkaloids from Mycetia effusa (Myrioneuron effusum) - Xiao-Hui Li; Jia-Hui Zhang; Yu Zhang; Ying-Tong Di; Yu-Cheng Gu; Mingming Cao; Xiao-Jiang Hao (Phytochemistry Letters, 2023)

Two new lignans from the herbaceous stems of Ephedra intermedia - Xi-Ling Fan; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Ying-Jie Ren; Xin-Yi Ma; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2023)

Immunochromatographic Assay based on Sc-TCPP 3D MOF for the rapid detection of imidacloprid in food samples - Ying Wang; Meng Zhang; Tong Bu; Feier Bai; Shuang Zhao; Yuanyuan Cao; Kunyi He; Haiyu Wu; Jia Xi; Li Wang (Food Chemistry, 2023)

Magnetically-oriented porous hydrogel advances wearable electrochemical solidoid sensing heavy metallic ions - Wanxin Tang; Zhen Gu; Yao Chu; Jian Lv; Li Fan; Xinling liu; Feng Wang; Ye Ying; Jian Zhang; Yuning Jiang; Jiaying Cao; Anni Zhu; et al. (Chemical Engineering Journal, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

Radical chemistry, degradation mechanism and toxicity evolution of BPA in the UV/chlorine and UV/H2O2 - Ying Cao; Jun Yao; Tatjana Šolević Knudsen; Wancheng Pang; Junjie Zhu; Bang Liu; Hao Li; Miaomiao Li; Jianchao Su (Chemosphere, 2023)

Co-products recovery does not necessarily mitigate environmental and economic tradeoffs in lithium-ion battery recycling - Yuanyu Cao; Liang Li; Ying Zhang; Zengwen Liu; Liqi Wang; Fan Wu; Jing You (Resources, Conservation and Recycling, 2023)

Puerol and pueroside derivatives from Pueraria lobata and their anti-inflammatory activity - Ying-Jie Sun; Shi-Jie Cao; Feng-Ni Liang; Jin-Yan Li; Xiang-Yu Zhang; Wei Li; Li-Qin Ding; Feng Qiu (Phytochemistry, 2023)

A numerical analysis of sloshing dynamics of two-layer liquid with a free surface - Weinan Cao; Xiaoming Li; Ying Gao; Xiaochen Li; Zeng Liu (Ocean Engineering, 2023)

TroTNFSF6, a tumor necrosis factor ligand superfamily member, promotes antibacterial immune response of golden pompano, Trachinotus ovatus - Chunsheng Liu; Lu Wang; Xiaojuan Chen; Zhiru Liu; Yang Shen; Ying Wu; Yongcan Zhou; Jianlong Li; Zhenjie Cao; Yun Sun (Fish & Shellfish Immunology, 2023)

Optimistic contributions of plant growth-promoting bacteria for sustainable agriculture and climate stress alleviation - Mengyuan Cao; Mathiyazhagan Narayanan; Xiaojun Shi; Xinping Chen; Zhenlun Li; Ying Ma (Environmental Research, 2023)

Experimental studies on shear behavior of steel-UHPC composite beam with hot rolled shape steel - Xudong Zhao; Xudong Shao; Junhui Cao; Zongxuan Shao; Rongjun Ying-Li (Engineering Structures, 2023)

A novel universal strategy for fabricating soybean protein adhesive with excellent adhesion and anti-mildew performances - Mingyang Bai; Ying Zhang; Yanyan Bian; Qiang Gao; Sheldon Q. Shi; Jinfeng Cao; Qiuhui Zhang; Jianzhang Li (Chemical Engineering Journal, 2023)

Degradation of three typical hydroxamic acids collectors via UVA-B activated H2O2 and persulfate: Kinetics, transformation pathway, DFT calculation and toxicity evaluation - Wancheng Pang; Jun Yao; Tatjana Šolević Knudsen; Ying Cao; Bang Liu; Hao Li; Miaomiao Li; Junjie Zhu (Chemical Engineering Journal, 2023)

ER stress-enhanced HMGA2 plays an important role in Cr (VI)-induced glycolysis and inhibited oxidative phosphorylation by targeting the transcription of ATF4 - Shengxiang Luo; Cong Zhang; Zeyun Gao; Liping Jiang; Qiujuan Li; Xiaoxia Shi; Ying Kong; Jun Cao (Chemico-Biological Interactions, 2023)

Protective effects of sinomenine hydrochloride on lead-induced oxidative stress, inflammation, and apoptosis in mouse liver - Ying Li; Wenjie Cai; Zichun Ai; Chenyu Xue; Rujing Cao; Na Dong (Environmental Science and Pollution Research, 2023)

Influence of different kinds of incinerators on PCDD/Fs: a case study of emission and formation pathway - Yuxuan Ying; Liang Xu; Xiaoqing Lin; Hao Zhang; Xiaodong Li; Shengyong Lu; Yang Cao; Jisheng Long (Environmental Science and Pollution Research, 2023)

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

Mitigation of atrazine-induced oxidative stress on soybean seedlings after co-inoculation with atrazine-degrading bacterium Arthrobacter sp. DNS10 and inorganic phosphorus-solubilizing bacterium Enterobacter sp. P1 - Zhao Jiang; Qi Shao; Yuxin Chu; Ning An; Bo Cao; Zheyi Ren; Jin Li; Jianhua Qu; Maofeng Dong; Ying Zhang (Environmental Science and Pollution Research, 2022)

A Facile, Label-free and Versatile Fluorescence Sensing Nanoplatform Based on Titanium Carbide Nanosheets for the Detection of Various Targets - Meishuang Liang; Bixia Lin; Zhijiao Tang; Li Zhang; Manli Guo; Yujuan Cao; Yumin Wang; Ying Yu (Journal of Fluorescence, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

PDGFD switches on stem cell endothelial commitment - Weisi Lu; Peipei Xu; Boxiong Deng; Jianing Zhang; Ying Zhan; Xianchai Lin; Xiangzhong Xu; Zhaoxia Xia; Xiaoxi Yang; Xiaoling Zeng; Lijuan Huang; Bingbing Xie; et al. (Angiogenesis, 2022)
The critical factors regulating stem cell endothelial commitment and renewal remain not well understood. Here, using loss- and gain-of-function assays together with bioinformatic analysis and multiple model systems, we show that PDGFD is an essential factor that switches on endothelial commitment of embryonic stem cells (ESCs). PDGFD genetic deletion or knockdown inhibits ESC differentiation into EC lineage and increases ESC self-renewal, and PDGFD overexpression activates ESC differentiation towards ECs. RNA sequencing reveals a critical requirement of PDGFD for the expression of vascular-differentiation related genes in ESCs. Importantly, PDGFD genetic deletion or knockdown increases ESC self-renewal and decreases blood vessel densities in both embryonic and neonatal mice and in teratomas. Mechanistically, we reveal that PDGFD fulfills this function via the MAPK/ERK pathway. Our findings provide new insight of PDGFD as a novel regulator of ESC fate determination, and suggest therapeutic implications of modulating PDGFD activity in stem cell therapy.

Enhanced M-CSF/CSF1R Signaling Closely Associates with PrPSc Accumulation in the Scrapie-Infected Cell Line and the Brains of Scrapie-Infected Experimental Rodents - Ying Xia; Cao Chen; Jia Chen; Chao Hu; Wei Yang; Lin Wang; Lian Liu; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Qi Shi; Zhi-Bao Chen; et al. (Molecular Neurobiology, 2022)

Differential expression and functional analysis of circRNA in the ovaries of Yili geese at different egg-laying stages - Xiao-yu Zhao; Ying-ping Wu; Hai-ying Li; Yan Cao; Zhi-yong Mei; Jia-hui Li (Genes & Genomics, 2022)

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Family–level phylogeny of infraorder Systellognatha (Insecta: Plecoptera) inferred from mitochondrial genomes - Ying Wang; Jinjun Cao; Dávid Murányi; Xuan Guo; Caiyue Guo; Weihai Li (Zoologica Scripta, 2022)
Systellognatha is a monophyletic group within stoneflies containing seven families in two superfamilies. However, the family–level phylogeny within Systellognatha is largely unresolved, with some controversial hypotheses generated by molecular data. In this study, we sequenced one complete and three nearly complete mitochondrial genomes (mitogenomes) representing three systellognathan families (including one newly described family), to recover the phylogeny of all seven extant systellognathan families. We tested the effect of heterogeneous sequence divergence within mitogenome sequences on phylogenetic reconstruction. To study incongruent topologies supported by different datasets, we also utilized four–cluster likelihood mapping to elucidate these phylogenetic questions. We found a low degree of compositional heterogeneity in systellognathan mitogenomes. Our results showed that phylogenetic analyses with various datasets under site–homogeneous models failed to recover the Perloidea and Pteronarcyoidea as monophyletic groups. However, Bayesian inference with a site–heterogeneous model (CAT + GTR) recovered Perloidea as monophyletic. Our results confirm a sister–group relationship between Chloroperlidae and Perlodidae. Despite all phylogenetic analyses failed to recover the Pteronarcyoidea as monophyletic, the analyses with site–heterogeneous model based on PCG12, PCG12R and PCGR datasets reconstructed the same relationships among Pteronarcyidae, Peltoperlidae, Styloperlidae and Perloidea. Our study shows the power of the site–heterogeneous models in resolving phylogeny within Systellognatha and provides a new insight into the phylogeny of this group.

Decreasing magnitude of soil erosion along vegetation succession on sloping farmland in the Loess Plateau of China: 5 years field monitoring evidence - Yue Liang; Ju-ying Jiao; Bing-zhe Tang; Bin-ting Cao; Hang Li (Journal of Mountain Science, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Nile tilapia TRIM39 recruits I3K413 and I3KL45 as adaptors and is involved in the NF‐κB pathway - Feng‐ying Gao; Xin Zhou; Mai‐xin Lu; Miao Wang; Zhi‐gang Liu; Jiang‐meng Cao; Xiao‐li Ke; Meng‐meng Yi (Journal of Fish Biology, 2022)
Tripartite motif (TRIM) proteins play a regulatory function in cancer, cell apoptosis and innate immunity. To understand the role of TRIM39 in Nile tilapia ( Oreochromis niloticus ), TRIM39 cDNA was isolated. The total length of TRIM39 cDNA was 5025 bp. The deduced OnTRIM39 protein contains 549 amino acids and has conserved domains of the TRIM family, which are the RING, B‐box, coiled‐coil and PRY‐SPRY domains. OnTRIM39 mRNA was widely expressed in various tissues. After challenge with Streptococcus agalactiae and stimulation with polyinosinic polycytidylic acid [poly (I:C)] and lipopolysaccharides (LPS), the amount of OnTRIM39 transcript was changed in various tested tissues. OnTRIM39 overexpression increased NF‐κB activity. OnTRIM39 was present in the cytoplasm. Mass spectrometry of proteins pulled down with recombinant OnTRIM39 showed that 250 proteins potentially interact with OnTRIM39. The authors selected I3K4I3 from the 250 candidate proteins to verify its interaction with TRIM39. They also selected I3KL45, a member of the same 14‐3‐3 protein family, to verify its interaction with TRIM39. The results of pull‐down assays showed that OnTRIM39 interacted with both I3K413 and I3KL45. These results contribute to further study of the innate immune mechanism of tilapia.

lncRNA BDNF-AS Attenuates Propofol-Induced Apoptosis in HT22 Cells by Modulating the BDNF/TrkB Pathway - Yu-Hai Xu; Yuan Luo; Jiang-Bei Cao; Yan-Hong Liu; Yu-Xiang Song; Xiao-Ying Zhang; Qiang Fu; Wei-Dong Mi; Hao Li (Molecular Neurobiology, 2022)
Propofol is widely used as an intravenous anesthetic in clinical practice. Previous studies have indicated that propofol induces apoptosis in neurons. Brain-derived neurotrophic factor (BDNF), a neurotrophic factor, is associated with neuronal apoptosis. BDNF-AS, a relatively conserved long non-coding RNA, can reverse the transcription of BDNF. This study aimed to investigate the involvement of BDNF-AS in propofol-induced apoptosis in HT22 cells. HT22 cells were treated with various concentrations of propofol at different time points. BDNF-AS was silenced using BDNF-AS-targeting siRNA. TrkB was antagonized by the TrkB inhibitor, ANA-12. Flow cytometry, quantitative reverse-transcription PCR, and western blotting were performed to analyze apoptosis and the expression of genes and proteins, respectively. In propofol-treated HT22 cells, BDNF-AS was upregulated, and BDNF was downregulated in a time- and dose-dependent manner. BDNF-AS downregulation mediated by siRNA mitigated apoptosis, upregulated the expression of Bcl-2, and downregulated the expression of Bax and caspase-3, 7, and 9. ANA-12 downregulated the expression of Bcl-2, upregulated the expression of Bax and caspase-3, 7, and 9, and increased apoptosis. Our study implied that inhibition of BDNF-AS can decrease propofol-induced apoptosis by activating the BDNF/TrkB pathway. Thus, the BDNF-AS-BDNF/TrkB signaling pathway may be a valuable target for treating propofol-induced neurotoxicity.

Effects of long-term exposure of norfloxacin on the HPG and HPT axes in juvenile common carp - Si-Qi Zhang; Xue-Li Zhao; Shu-Wen He; Shao-Ying Xing; Zhi-Han Cao; Ping Li; Zhi-Hua Li (Environmental Science and Pollution Research, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Structural Characterization and Immunoenhancing Effects of a Polysaccharide from the Soft Coral Lobophytum sarcophytoides - Xueqin Cao; Qian Zhang; Yanglu Zhu; Siju Li; Ying Cai; Pei Li; Deliang Liu; Yun Leng; Simin Ye; Zengmei Xu; Hao Li; Baochun Shen; et al. (Marine Biotechnology, 2022)

The association between short-term ambient air pollution and acne vulgaris outpatient visits: a hospital-based time-series analysis in Xi’an - Xiang Li; Yi Cao; Shu-Jie An; Ying Xiang; He-Xiang Huang; Bin Xu; Yao Zhang; Ya-Fei Li; Yuan-Gang Lu; Tong-Jian Cai (Environmental Science and Pollution Research, 2022)

Fruit and vegetable consumption, cardiovascular disease, and all-cause mortality in China - Jun Wang; Fangchao Liu; Jianxin Li; Keyong Huang; Xueli Yang; Jichun Chen; Xiaoqing Liu; Jie Cao; Shufeng Chen; Chong Shen; Ling Yu; Fanghong Lu; et al. (Science China Life Sciences, 2022)

Experimental Analysis on the Optimal Excitation Wavelength for Fine-Grained Identification of Refined Oil Pollutants on Water Surface Based on Laser-Induced Fluorescence - Ming Xie; Yunpeng Jia; Ying Li; Xiaohua Cai; Kai Cao (Journal of Fluorescence, 2022)

Mongoliitalea daihaiensis sp. nov., isolated from Daihai Lake in Inner Mongolia - Kai Jiang; Bo Yuan; Chun Ling Cao; Chen Ying Zhang; Ruo Xuan Li; Yan An (Archives of Microbiology, 2022)

Two new nor-sesquiterpenoids from Fusarium tricinctum , an endophytic fungus isolated from Ligusticum chuanxiong - Yu-Mei Cao; Da-Le Guo; Meng-Ying Jin; Lu Tan; Tian-Long Yang; Fang Deng; Yu-Cheng Gu; Xiao-Hua Li; Zhi-Xing Cao; Yun Deng (Natural Product Research, 2021)

Paraburkholderia sp. GD17 improves rice seedling tolerance to salinity - Ruanming Zhu; Yuting Cao; Guangzhe Li; Ying Guo; Lianju Ma; Ning Bu; Lin Hao (Plant and Soil, 2021)

Two new norsesquiterpenoids with estrogenic activity from the stems and leaves of Dioscorea oppositifolia L - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Bei-Bei Zhang; Yan-Ling Liu; Meng-Na Wang; Yan-Li Zhang; Wei-Sheng Feng; Xiao-Ke Zheng (Natural Product Research, 2021)

Local climate adaptation and gene flow in the native range of two co‐occurring fruit moths with contrasting invasiveness - Li‐Jun Cao; Bing‐Yan Li; Jin‐Cui Chen; Jia‐Ying Zhu; Ary A. Hoffmann; Shu‐Jun Wei (Molecular Ecology, 2021)
Invasive species pose increasing threats to global biodiversity and ecosystems. While previous studies have characterized successful invaders based on ecological traits, characteristics related to evolutionary processes have rarely been investigated. Here we compared gene flow and local adaptation using demographic analyses and outlier tests in two co‐occurring moth pests across their common native range of China, one of which (the peach fruit moth, Carposina sasakii ) has maintained its native distribution, while the other (the oriental fruit moth, Grapholita molesta ) has expanded its range globally during the past century. We found that both species showed a pattern of genetic differentiation and an evolutionary history consistent with a common southwestern origin and northward expansion in their native range. However, for the noninvasive species, genetic differentiation was closely aligned with the environment, and there was a relatively low level of gene flow, whereas in the invasive species, genetic differentiation was associated with geography. Genome scans indicated stronger patterns of climate‐associated loci in the noninvasive species. While strong local adaptation and reduced gene flow across its native range may have decreased the invasiveness of C . sasakii , this requires further validation with additional comparisons of invasive and noninvasive species across their native range.

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

Altered gray matter structural covariance networks at both acute and chronic stages of mild traumatic brain injury - Jie Song; Jie Li; Lixiang Chen; Xingqi Lu; Senning Zheng; Ying Yang; Bolin Cao; Yihe Weng; Qinyuan Chen; Jianping Ding; Ruiwang Huang (Brain Imaging and Behavior, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Selenium Supplementation Protects Against Lipopolysaccharide-Induced Heart Injury via Sting Pathway in Mice - Xuan Wang; Bin Yang; Hui-Li Cao; Rui-Ying Wang; Zhao-Yang Lu; Rui-Fang Chi; Bao Li (Biological Trace Element Research, 2021)

A novel homozygous nonsense mutation in the CA2 gene (c.368G>A, p.W123X) linked to carbonic anhydrase II deficiency syndrome in a Chinese family - Yan Yang; Nie Tang; Ying Zhu; Lei Zhang; Xu Cao; Limei Liu; Wei Xia; Pengqiu Li; Yi Yang (Metabolic Brain Disease, 2021)

Editorial Expression of Concern: The bio-mitigation of acetochlor in soil using Rhodopseudomonas capsulata in effluent after wastewater treatment - Pan Wu; Bo Cao; Ying Zhang; Wenbin Li; Yanling Wang; Yuan Wu; Ning Li (Journal of Soils and Sediments, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

The Association Between Trace Elements Exposure and the Cognition in the Elderly in China - Ling Gu; Jinhui Yu; Yong Fan; Sufang Wang; Linsheng Yang; Kaiyong Liu; Qunan Wang; Guimei Chen; Dongmei Zhang; Ying Ma; Li Wang; Annuo Liu; et al. (Biological Trace Element Research, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

SCGN-regulated Stage-wise SNARE Assembly: Novel Insight into Synaptic Exocytosis - Ying Lv; Sunmin Xiang; Renxian Cao; Li Wu; Jing Yang (Neuroscience Bulletin, 2020)

AMPK Ameliorates Tau Acetylation and Memory Impairment Through Sirt1 - Lin Wang; Fang-Xiao Shi; Na Li; Yun Cao; Ying Lei; Jian-Zhi Wang; Qing Tian; Xin-Wen Zhou (Molecular Neurobiology, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Common transcriptome, plasma molecules, and imaging signatures in the aging brain and a Mendelian neurovascular disease, cerebral cavernous malformation - Janne Koskimäki; Sean P. Polster; Yan Li; Sharbel Romanos; Abhinav Srinath; Dongdong Zhang; Julián Carrión-Penagos; Rhonda Lightle; Thomas Moore; Seán B. Lyne; Agnieszka Stadnik; Kristina Piedad; et al. (GeroScience, 2020)

Associations of egg consumption with incident cardiovascular disease and all-cause mortality - Xue Xia; Fangchao Liu; Xueli Yang; Jianxin Li; Jichun Chen; Xiaoqing Liu; Jie Cao; Chong Shen; Ling Yu; Yingxin Zhao; Xianping Wu; Liancheng Zhao; et al. (Science China Life Sciences, 2020)

Methyl 3-(4-hydroxyphenyl) propionate modulates plant growth and secondary metabolite accumulation by inducing metabolic changes in Perilla frutescens - Jinhu Ma; Yongheng Cao; Liangliang Sun; Ying Li; Qiong Ju; Xiaohuan Yang; Jin Xu (Plant and Soil, 2020)

Upregulation of AMPK Ameliorates Alzheimer’s Disease-Like Tau Pathology and Memory Impairment - Lin Wang; Na Li; Fang-Xiao Shi; Wei-Qi Xu; Yun Cao; Ying Lei; Jian-Zhi Wang; Qing Tian; Xin-Wen Zhou (Molecular Neurobiology, 2020)

Development of a specific AFLP-based SCAR marker for Chinese Race 34MKG of Puccinia graminis f. sp. tritici - Si Chen; Xue Yang; Wen-gong Huang; Yan Liu; Ying Yu; Guang-wen Wu; Shu-quan Zhang; Tian-ya Li; Yuan-yin Cao (Molecular Biology Reports, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Role of T-type Calcium Channels in Generating Hyperexcitatory Behaviors during Emergence from Sevoflurane Anesthesia in Neonatal Rats - Feng-Yan Shen; Byung-Gun Lim; Wen Wen; Yu Zhang; Bo Cao; Yue-Guang Si; Li-Qing Ma; Meng Deng; Yang In Kim; Young-Beom Kim; Ying-Wei Wang (Neuroscience Bulletin, 2020)

Identification and characterization of a novel gene-encoded antioxidant peptide obtained from amphibian skin secretions - Ying Wang; Xiaoqing Cao; Zhe Fu; Siyuan Wang; Xiaojie Li; Naixin Liu; Zhuo Feng; Meifeng Yang; Jing Tang; Xinwang Yang (Natural Product Research, 2020)

Association of Blood Lead Levels with the Risk of Depressive Symptoms in the Elderly Chinese Population: Baseline Data of a Cohort Study - Yong Fan; Jie Sheng; Chunmei Liang; Linsheng Yang; Kaiyong Liu; Qunan Wang; Dongmei Zhang; Ying Ma; Xiude Li; Shaoyu Xie; Hongjuan Cao; Sufang Wang; et al. (Biological Trace Element Research, 2020)

Fractional vegetation coverage response to climatic factors based on grey relational analysis during the 2000-2017 growing season in Sichuan Province, China - Peng Li; Zhengwei He; Dong He; Dongjian Xue; Ying Wang; Shisong Cao (International Journal of Remote Sensing, 2020)

Enhanced stability of a rumen-derived xylanase using SpyTag/SpyCatcher cyclization - Ye-Bo Zhou; Jia-Wen Cao; Xiao-Bao Sun; Huan Wang; De-Ying Gao; Yang-Nan Li; Kai-Yue Wu; Jia-Kun Wang; Guo-Ying Qian; Qian Wang (World Journal of Microbiology and Biotechnology, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Comparison of two commonly used methods for stimulating T cells - Juanjuan Jiao; Xincheng Zhao; Ruixia Hou; Ying Wang; Wenjuan Chang; Nannan Liang; Yanmin Liu; Jianxiao Xing; Yue Cao; Xiaofang Li; Kaiming Zhang (Biotechnology Letters, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Cryobacterium tepidiphilum sp. nov., isolated from rhizosphere soil of lettuce (var. ramosa Hort.) - Ying Wang; Peng Cao; Peng Sun; Junwei Zhao; Xiujun Sun; Ji Zhang; Chenxu Li; Wensheng Xiang; Xiangjing Wang (Antonie van Leeuwenhoek, 2019)

Early diagenesis of redox-sensitive trace metals in the northern Okinawa Trough - Xiaojing Wang; Li Li; Jihua Liu; Yonghua Wu; Jingjing Gao; Peng Cao; Ying Zhang; Xuefa Shi (Acta Oceanologica Sinica, 2019)

Recent Developments in Local Wave Decomposition Methods for Understanding Seismic Data: Application to Seismic Interpretation - Ya-juan Xue; Jun-xing Cao; Xing-jian Wang; Ying-xiang Li; Jiang Du (Surveys in Geophysics, 2019)

Nanopore sequencing: a rapid solution for infectious disease epidemics - Ying Cao; Jing Li; Xin Chu; Haizhou Liu; Wenjun Liu; Di Liu (Science China Life Sciences, 2019)

Development of a reverse genetics system for Japanese encephalitis virus strain SA14-14-2 - Guohua Li; Hongli Jin; Xin Nie; Yongkun Zhao; Na Feng; Zongxi Cao; Shuyi Tan; Bo Zhang; Weiwei Gai; Feihu Yan; Ling Li; Ying Zhang; et al. (Virus Genes, 2019)

The bio-mitigation of acetochlor in soil using Rhodopseudomonas capsulata in effluent after wastewater treatment - Pan Wu; Bo Cao; Ying Zhang; Wenbin Li; Yanling Wang; Yuan Wu; Ning Li (Journal of Soils and Sediments, 2019)

Terrain relief periods of loess landforms based on terrain profiles of the Loess Plateau in northern Shaanxi Province, China - Jianjun Cao; Guoan Tang; Xuan Fang; Jilong Li; Yongjuan Liu; Yiting Zhang; Ying Zhu; Fayuan Li (Frontiers of Earth Science, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Hsc70 Interacts with β4GalT5 to Regulate the Growth of Gliomas - Guan Sun; Ying Cao; Xueliang Dai; Min Li; Jun Guo (NeuroMolecular Medicine, 2019)

The Arabidopsis AGAMOUS 5′-UTR represses downstream gene translation - Ying Cao; Ying Wang; Yan Li; Jing Yang; Ligeng Ma (Science China Life Sciences, 2019)

MHC class IIA polymorphisms and their association with resistance–susceptibility to Streptococcus agalactiae in Nile tilapia, Oreochromis niloticus - Feng‐Ying Gao; Dong Zhang; Mai‐Xin Lu; Jian‐Meng Cao; Zhi‐Gang Liu; Xiao‐Li Ke; Miao Wang; De‐Feng Zhang; Meng‐Meng Yi (Journal of Fish Biology, 2018)
The association between major histocompatibility complex (MHC) class IIA polymorphisms and the severity of infection by Streptococcus agalactiae was investigated using 40 susceptible and 40 resistant individuals of Nile tilapia Oreochromis niloticus . Twenty‐five alleles were identified from 80 individuals, which belong to 22 major allele types. High polymorphism of mhcIIa gene and at least two loci were discovered in O. niloticus . In peptide‐binding region (PBR) and non‐PBR, the ratio of nonsynonymous substitution ( dN ) to synonymous substitution ( dS ) was 1.294 (>1) and 1.240 (>1), suggesting that the loci are evolving under positive balancing selection. Association analysis showed that the allele, orni‐daa*0501 , was significantly associated with resistance to S. agalactiae , while the alleles, orni‐daa*1101 , orni‐daa*1301 , orni‐daa*1401 and orni‐daa*1201 , were associated with susceptibility to S. agalactiae . To confirm these correlations, another independent challenge experiment was performed in the Huizhou population of the O. niloticus . The frequency distribution showed that the orni‐daa*1101 allele was significantly more frequent in the Huizhou‐Susceptible group (HZ‐SG) than in the Huizhou‐Resistant group (HZ‐RG) ( P orni‐daa*0501 did not present in HZ‐SG and HZ‐RG and the distribution frequencies of the orni‐daa*1201 , orni‐daa*1301 and orni‐daa*1401 alleles were not significantly more frequent in HZ‐SG than in HZ‐RG. These results indicate that the orni‐daa*1101 allele confers susceptibility to S. agalactia infection. These results suggest that the diversity of exon 2 of mcaIIa alleles could be used to explore the association between disease susceptibility or resistance and the multiformity of mcaIIa and to achieve the molecular‐assisted selection of O. niloticus with enhanced disease resistance.

Polyphenolic compounds from Malus hupehensis and their free radical scavenging effects - Qingwen Hu; Ying-Ying Chen; Qi-Yang Jiao; Afsar Khan; Jimiao Shan; Gui-Dong Cao; Feng Li; Chao Zhang; Hong-Xiang Lou (Natural Product Research, 2018)

Anxiolytic potency of iridoid fraction extracted from Valeriana jatamansi Jones and its mechanism: a preliminary study - Xue-Mei Zhang; Jia-Li Zhu; Yong Sun; Yao-Lan Dai; Xiu Chen; Jia-Hong Cao; Ruo-Cong Yang; Chang Chen; Chao-Ying Ma; Tian-E Zhang; Yun-Hui Chen; Zhi-Yong Yan (Natural Product Research, 2018)

Evaluation of turfgrid porous pavements for urban stormwater management in Xiamen Island, Southeast China - Baoli Liu; Wenzhi Cao; Ying Li (Sustainable Water Resources Management, 2018)

Seawater acidification affects the immune enzyme activities of the Manila clam Ruditapes philippinarum - Zhongming Huo; Xiangyu Meng; Rbbani Md.Golam; Weinan Cao; Qidi Wu; Ying Li; Jingtian Wang; Hongmei Yuan; Feng Yang; Xiwu Yan (Journal of Oceanology and Limnology, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Growth, physiological responses, and copper accumulation in seven willow species exposed to Cu—a hydroponic experiment - Yini Cao; Ying Zhang; Chuanxin Ma; Haimei Li; Jianfeng Zhang; Guangcai Chen (Environmental Science and Pollution Research, 2018)

Identification of a Splicing Mutation in ITPR1 via WES in a Chinese Early-Onset Spinocerebellar Ataxia Family - Li Wang; Ying Hao; Peng Yu; Zhenhua Cao; Jin Zhang; Xin Zhang; Yuanyuan Chen; Hao Zhang; Weihong Gu (The Cerebellum, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

Functional analysis of amino acids at stalk/head interface of human parainfluenza virus type 3 hemagglutinin-neuraminidase protein in the membrane fusion process - Jingjing Jiang; Hongling Wen; Miaomiao Chi; Ying Liu; Jingxue Liu; Zhankui Cao; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2018)

The mitochondrial genome of a stonefly species, Cerconychia sapa (Plecoptera: Styloperlidae) - Ying Wang; Jinjun Cao; Beibei Lei; Weihai Li (Conservation Genetics Resources, 2018)

Ideal cardiovascular health and incidence of atherosclerotic cardiovascular disease among Chinese adults: the China-PAR project - Chao Han; Fangchao Liu; Xueli Yang; Jichun Chen; Jianxin Li; Jie Cao; Ying Li; Chong Shen; Ling Yu; Zhendong Liu; Xianping Wu; Liancheng Zhao; et al. (Science China Life Sciences, 2018)

A Quninolylthiazole Derivatives as an ICT-Based Fluorescent Probe of Hg(II) and its Application in Ratiometric Imaging in Live HeLa Cells - Jian-Ying Bai; Yu-Zhong Xie; Chang-Jiang Wang; Shu-Qing Fang; Lin-Nan Cao; Ling-Li Wang; Jing-Yi Jin (Journal of Fluorescence, 2018)

Peripheral Leptin Signaling Mediates Formalin-Induced Nociception - Zhi-Jing Hu; Wei Han; Chang-Qing Cao; Qi-Liang Mao-Ying; Wen-Li Mi; Yan-Qing Wang (Neuroscience Bulletin, 2018)

Porcine teschovirus 2 induces an incomplete autophagic response in PK-15 cells - Yuanxing Gu; Yingshan Zhou; Xinfeng Shi; Yongping Xin; Ying Shan; Cong Chen; Tong Cao; Weihuan Fang; Xiaoliang Li (Archives of Virology, 2018)

Plasma Biomarkers of Inflammation Reflect Seizures and Hemorrhagic Activity of Cerebral Cavernous Malformations - Romuald Girard; Hussein A. Zeineddine; Maged D. Fam; Anoop Mayampurath; Ying Cao; Changbin Shi; Robert Shenkar; Sean P. Polster; Michael Jesselson; Ryan Duggan; Abdul-Ghani Mikati; Gregory Christoforidis; et al. (Translational Stroke Research, 2018)

An expression atlas of miRNAs in Arabidopsis thaliana - Le Xu; Yugang Hu; Ying Cao; Jingrui Li; Ligeng Ma; Yan Li; Yijun Qi (Science China Life Sciences, 2018)

The mitochondrial genome of Mesocapnia daxingana (Plecoptera: Capniidae) - Ying Wang; Jinjun Cao; Weihai Li; Xiling Chen (Conservation Genetics Resources, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Two new phenolic glycosides from the stem of Zanthoxylum armatum DC - Tao Guo; Li-Ping Dai; Xiao-Feng Tang; Tong-Tong Song; Ya Wang; Ai-Hong Zhao; Ying-Ying Cao; Jun Chang (Natural Product Research, 2017)

MiR-340 Regulates Fibrinolysis and Axon Regrowth Following Sciatic Nerve Injury - Shiying Li; Ruirui Zhang; Ying Yuan; Sheng Yi; Qianqian Chen; Leilei Gong; Jie Liu; Fei Ding; Zheng Cao; Xiaosong Gu (Molecular Neurobiology, 2017)

Effects of endogenous hormones on variation of shoot branching in a variety of non-heading Chinese cabbage and related gene expression - Xue-Wei Cao; Hong-Mi Cui; Yuan Yao; Ai-Sheng Xiong; Xi-Lin Hou; Ying Li (Journal of Plant Biology, 2017)

The contribution of denitrification and anaerobic ammonium oxidation to N2 production in mangrove sediments in Southeast China - Wenzhi Cao; Qingsong Guan; Ying Li; Min Wang; Baoli Liu (Journal of Soils and Sediments, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Construction of a recombinant duck enteritis virus vaccine expressing hemagglutinin of H9N2 avian influenza virus and evaluation of its efficacy in ducks - Ying Sun; Chenghuai Yang; Junping Li; Ling Li; Minghui Cao; Qihong Li; Huijiao Li (Archives of Virology, 2017)

The P450 oxidoreductase (POR) rs2868177 and cytochrome P450 (CYP) 2B6*6 polymorphisms contribute to the interindividual variability in human CYP2B6 activity - Li-chen Gao; Fang-qun Liu; Li Yang; Lin Cheng; Hai-ying Dai; Ran Tao; Shi-Peng Cao; Di Wang; Jie Tang (European Journal of Clinical Pharmacology, 2016)

Selenium Deficiency Facilitates Inflammation Following S. aureus Infection by Regulating TLR2-Related Pathways in the Mouse Mammary Gland - Xuejiao Gao; Zecai Zhang; Ying Li; Peng Shen; Xiaoyu Hu; Yongguo Cao; Naisheng Zhang (Biological Trace Element Research, 2016)

Selenium Deficiency Deteriorate the Inflammation of S. aureus Infection via Regulating NF-κB and PPAR-γ in Mammary Gland of Mice - Xuejiao Gao; Zecai Zhang; Ying Li; Xiaoyu Hu; Peng Shen; Yunhe Fu; Yongguo Cao; Naisheng Zhang (Biological Trace Element Research, 2016)

Development of microsatellite markers for the plant bug, Pachypeltis micranthus (Hemiptera: Miridae) - Jia-Ying Zhu; Sang-Zi Ze; Li-Jun Cao; Bin Yang (Applied Entomology and Zoology, 2016)

Immunogenicity of transmissible gastroenteritis virus (TGEV) M gene delivered by attenuated Salmonella typhimurium in mice - Ying Qing; Jiawen Liu; Xiaobo Huang; Yaqing Li; Yudi Zhang; Jie Chen; Xintian Wen; Sanjie cao; Yiping Wen; Rui Wu; Qigui Yan; Xiaoping Ma (Virus Genes, 2016)

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco - Jun-Ru Hu; Yan-Hua Huang; Guo-Xia Wang; Ying-Xia Wu; Jian-An Xian; An-Li Wang; Jun-Ming Cao (Fish Physiology and Biochemistry, 2016)

Fatal pneumonia cases caused by human adenovirus 55 in immunocompetent adults - Shu-Yan Zhang; Yan-Ping Luo; Dou-Dou Huang; Hang Fan; Qing-Bin Lu; Ying Wo; Gang Chen; Xiao-Ai Zhang; Yan Li; Yi-Gang Tong; Wu-Chun Cao; Wei Liu (Infectious Diseases, 2016)

Protective action of the phyllanthin against carbon tetrachloride-induced hepatocyte damage in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (In Vitro Cellular & Developmental Biology - Animal, 2016)

A Study of 2,3,7,8-Tetrachlorodibenzo-p-dioxin Induced Liver Injury in Jian Carp (Cyprinus carpio var. Jian) Using Precision-Cut Liver Slices - Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Rui Jia; Guo-Jun Yin (Bulletin of Environmental Contamination and Toxicology, 2016)

QTL mapping for flowering time in different latitude in soybean - Sijia Lu; Ying Li; Jialin Wang; Peerasak Srinives; Haiyang Nan; Dong Cao; Yanping Wang; Jinliang Li; Xiaoming Li; Chao Fang; Xinyi Shi; Xiaohui Yuan; et al. (Euphytica, 2015)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

Rapid cloning and bioinformatic analysis of spinach Y chromosome-specific EST sequences - CHUAN-LIANG DENG; WEI-LI ZHANG; YING CAO; SHAO-JING WANG; SHU-FEN LI; WU-JUN GAO; LONG-DOU LU (Journal of Genetics, 2015)

GmmiR156b overexpression delays flowering time in soybean - Dong Cao; Ying Li; Jialin Wang; Haiyang Nan; Youning Wang; Sijia Lu; Qiong Jiang; Xiaoming Li; Danning Shi; Chao Fang; Xiaohui Yuan; Xiaohui Zhao; et al. (Plant Molecular Biology, 2015)

A novel large deletion mutation of FERMT1 gene in a Chinese patient with Kindler syndrome - Ying Gao; Jin-li Bai; Xiao-yan Liu; Yu-jin Qu; Yan-yan Cao; Jian-cai Wang; Yu-wei Jin; Hong Wang; Fang Song (Journal of Zhejiang University-SCIENCE B, 2015)

Effects of Graded Levels of Chromium Methionine on Performance, Carcass Traits, Meat Quality, Fatty Acid Profiles of Fat, Tissue Chromium Concentrations, and Antioxidant Status in Growing-Finishing Pigs - Yao-Yao Tian; Li-Min Gong; Jian-Xiang Xue; Jun Cao; Li-Ying Zhang (Biological Trace Element Research, 2015)

Protective effect of L-carnitine in cyclophosphamide-induced germ cell apoptosis - Bin Zhu; Yan-fei Zheng; Yue-ying Zhang; Yun-song Cao; Lei Zhang; Xin-gang Li; Teng Liu; Zhao-zhu Jiao; Qi Wang; Zhi-gang Zhao (Journal of Zhejiang University-SCIENCE B, 2015)

Celastrol Ameliorates EAE Induction by Suppressing Pathogenic T Cell Responses in the Peripheral and Central Nervous Systems - Ying Wang; Lu Cao; Li-min Xu; Fan-fan Cao; Bin Peng; Xue Zhang; Yu-fan Shen; Georges Uzan; Deng-hai Zhang (Journal of Neuroimmune Pharmacology, 2015)

Hepatoprotective and antioxidant effects of phyllanthin against carbon tetrachloride-induced liver injury in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (Aquaculture International, 2015)

Autophagy regulates insulin resistance following endoplasmic reticulum stress in diabetes - Ning Zhang; Ming-ming Cao; Han Liu; Guang-ying Xie; Yan-bo Li (Journal of Physiology and Biochemistry, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Ammonium-nitrogen-contaminated groundwater remediation by a sequential three-zone permeable reactive barrier (multibarrier) with oxygen-releasing compound (ORC)/clinoptilolite/spongy iron: column studies - Guoxin Huang; Fei Liu; Yingzhao Yang; Xiangke Kong; Shengpin Li; Ying Zhang; Dejun Cao (Environmental Science and Pollution Research, 2015)

Epidemical features of HAdV-3 and HAdV-7 in pediatric pneumonia in Chongqing, China - Ying Wo; Qing-Bin Lu; Dou-Dou Huang; Xiao-Kun Li; Chen-Tao Guo; Hong-Yu Wang; Xiao-Ai Zhang; Wei Liu; Wu-Chun Cao (Archives of Virology, 2015)

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Antidepressant-like effects of ferulic acid: involvement of serotonergic and norepinergic systems - Jianliang Chen; Dan Lin; Chong Zhang; Gaowen Li; Nianping Zhang; Lina Ruan; Qizhi Yan; Jianxin Li; Xuefeng Yu; Xupei Xie; Cong Pang; Liang Cao; et al. (Metabolic Brain Disease, 2015)

Effects of Chromium Methionine Supplementation on Growth Performance, Serum Metabolites, Endocrine Parameters, Antioxidant Status, and Immune Traits in Growing Pigs - Yao-Yao Tian; Li-Ying Zhang; Bing Dong; Jun Cao; Jian-Xiang Xue; Li-Min Gong (Biological Trace Element Research, 2014)

Effect of varying NaCl doses on flavonoid production in suspension cells of Ginkgo biloba: relationship to chlorophyll fluorescence, ion homeostasis, antioxidant system and ultrastructure - Ying Chen; Fangzhi Lin; Hua Yang; Li Yue; Fei Hu; Junlin Wang; Yongya Luo; Fuliang Cao (Acta Physiologiae Plantarum, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Upregulation of EHD2 after Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Ying Rui; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Maohong Cao (Journal of Molecular Neuroscience, 2014)

Preparation and Characterization of Activated Carbons from Peanut Shell and Rice Bran and a Comparative Study for Cr(VI) Removal from Aqueous Solution - Jing Zhang; Ruimin Wang; Xiaoyan Cao; Ying Li; Yeqing Lan (Water, Air, & Soil Pollution, 2014)

Origins of evaporites in the Middle Triassic Leikoupo Formation of the Sichuan Basin, southwest China and their geological implications - Ling Li; Xiucheng Tan; Jian Cao; Chun Zou; Xiong Ding; Guang Yang; Danling Ying (Carbonates and Evaporites, 2014)

E2F1-mediated DNA damage is implicated in 8-Cl-adenosine-induced chromosome missegregation and apoptosis in human lung cancer H1299 cells - Yu-Ying Han; Zhe Zhou; Ji-Xiang Cao; Ya-Qiong Jin; Shu-Yan Li; Ju-Hua Ni; Guo-Shun An; Yu-Xiang Zhang; Hong-Ti Jia (Molecular and Cellular Biochemistry, 2013)

Preliminary Extraction and Identification of the 44.5 kDa Outer Membrane Proteins Isolated from Bovine Fusobacterium necrophorum (AB) - Jing Xu; Li-Zhi Chen; Xiao-Ying Liu; Er-Kai Feng; Sun-Jie Wang; Yue Cao (Indian Journal of Microbiology, 2013)

The PpLTP1 Primary Allergen Gene is Highly Conserved in Peach and Has Small Variations in Other Prunus Species - Ying-tao Ma; Xiang Zhou; Zhong-shan Gao; Xiong-wei Li; Hui-juan Jia; Hong-xia Wu; Rang-jin Xie; Zhi-qiang Wang; Ming-liang Yu; Ke Cao; Shuang-jian Chen; Ying-hui Li; et al. (Plant Molecular Biology Reporter, 2013)

Whole transcriptome sequencing reveals genes involved in plastid/chloroplast division and development are regulated by the HP1/DDB1 at an early stage of tomato fruit development - Xiaofeng Tang; Zizhi Tang; Shengxiong Huang; Jikai Liu; Jia Liu; Wei Shi; Xuefen Tian; Yuxiang Li; Danfeng Zhang; Jian Yang; Yongfeng Gao; Deer Zeng; et al. (Planta, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Wip1 Phosphatase Involved in Lipopolysaccharide-Induced Neuroinflammation - Xiang Tan; Jingjing Zhang; Wei Jin; Lei Li; Wei Xu; Heyi Zheng; Ying Rui; Kaifu Ke; Ranran Zhou; Maohong Cao; Yongjin Pan (Journal of Molecular Neuroscience, 2013)

Up-regulating Blood Brain Barrier Permeability of Nanoparticles via Multivalent Effect - Xihui Gao; Jun Qian; Shuyan Zheng; Ying Xiong; Jiahao Man; Binxin Cao; Lu Wang; Shenghong Ju; Cong Li (Pharmaceutical Research, 2013)

Up-regulation of SGTB is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide - Maohong Cao; Wei Xu; Jian Yu; Heyi Zheng; Xiang Tan; Lei Li; Ying Rui; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Tao Tao; et al. (Journal of Molecular Histology, 2013)

Up-regulated expression of Bnip3L after intracerebral hemorrhage in adult rats - Ying Rui; Kaifu Ke; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Guangwei Zhao; Yilu Gao; Maohong Cao (Journal of Molecular Histology, 2013)

Increased Expression of Small Heat Shock Protein αB-crystallin After Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Lei Li; Ying Rui; Heyi Zheng; Xiang Tan; Wei Xu; Jianhua Cao; Jian Xu; Gang Cui; Guangfei Xu; Maohong Cao (Journal of Molecular Neuroscience, 2013)

Microdissection and painting of the Y chromosome in spinach (Spinacia oleracea) - Chuan-liang Deng; Rui-yun Qin; Ying Cao; Jun Gao; Shu-fen Li; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2013)

Neurotoxicity and Reactive Astrogliosis in the Anterior Cingulate Cortex in Acute Ciguatera Poisoning - Xu Zhang; Bing Cao; Jun Wang; Jin Liu; Vivian Oi Vian Tung; Paul Kwan Sing Lam; Leo Lai Chan; Ying Li (NeuroMolecular Medicine, 2013)

Genome-wide association study in Han Chinese identifies three novel loci for human height - Yongchen Hao; Xuehui Liu; Xiangfeng Lu; Xueli Yang; Laiyuan Wang; Shufeng Chen; Hongfan Li; Jianxin Li; Jie Cao; Jichun Chen; Ying Li; Liancheng Zhao; et al. (Human Genetics, 2013)

Upregulation of CBLL1 in rat brain cortex after lipopolysaccharide treated - Maohong Cao; Heyi Zheng; Xiang Tan; Wei Xu; Ying Rui; Lei Li; Xiaofei Liu; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Kaifu Ke; et al. (Journal of Molecular Histology, 2013)

Genetic diversity of Bartonella quintana in macaques suggests zoonotic origin of trench fever - Hao Li; Jie‐Ying Bai; Li‐Yuan Wang; Lin Zeng; Yan‐Sheng Shi; Zheng‐Liang Qiu; Hua‐Hu Ye; Xiao‐Fei Zhang; Qing‐Bin Lu; Michael Kosoy; Wei Liu; Wu‐Chun Cao (Molecular Ecology, 2013)
Bartonella quintana is a bacterium that causes a broad spectrum of diseases in humans including trench fever. Humans were previously considered to be the primary, if not the only, reservoir hosts for B. quintana . To identify the animal reservoir and extend our understanding of the ecological and evolutionary history of B. quintana , we examined blood samples from macaques and performed multilocus sequence typing ( MLST ) analysis. We demonstrated the prevalence of B. quintana infection was common in macaques from main primate centres in mainland C hina. Overall, 18.0% (59/328) of rhesus macaques and 12.7% (39/308) of cynomolgus macaques were found to be infected with B. quintana by blood culture and/or polymerase chain reaction. The infection was more frequently identified in juvenile and young monkeys compared with adult animals. In contrast with the relatively low level of sequence divergence of B. quintana reported in humans, our investigation revealed much higher genetic diversity in nonhuman primates. We identified 44 new nucleotide variable sites and 14 novel sequence types (STs) among the B. quintana isolates by MLST analysis. Some STs were found only in cynomolgus macaques, while some others were detected only in rhesus macaques, suggesting evidence of host‐cospeciation, which were further confirmed by phylogenetic analysis and Splits decomposition analysis. Our findings suggest that trench fever may primarily be a zoonotic disease with macaques as the natural hosts.

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

An L-Type Calcium Channel Agonist, Bay K8644, Extends the Window of Intervention Against Ischemic Neuronal Injury - Hong-hai Hu; Shu-ji Li; Pu Wang; Hua-cheng Yan; Xiong Cao; Feng-qin Hou; Ying-ying Fang; Xin-hong Zhu; Tian-ming Gao (Molecular Neurobiology, 2013)

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex - Li Ma; Yong Hong Cao; Ming Hui Cheng; Ying Huang; Ming He Mo; Yong Wang; Jian Zhong Yang; Fa Xiang Yang (Antonie van Leeuwenhoek, 2013)

Sequence characterization and expression pattern of BcMF21, a novel gene related to pollen development in Brassica campestris ssp. chinensis - Jingjing Jiang; Xiaolin Yu; Ying Miao; Li Huang; Lina Yao; Jiashu Cao (Molecular Biology Reports, 2012)

Circadian Rhythm in Serum Iron Levels - Guo Ying Cao; Yang Li; Peng Fei Jin; Xin Hu (Biological Trace Element Research, 2012)

Clinical significance of peritumoral lymphatic vessel density and lymphatic vessel invasion detected by D2-40 immunostaining in FIGO Ib1-IIa squamous cell cervical cancer - Ying Xiong; Li-Ping Cao; Hui-Lan Rao; Mu-Yan Cai; Li-Zhi Liang; Ji-Hong Liu (Cell and Tissue Research, 2012)

Continuous biosynthesis of abscisic acid (ABA) may be required for maintaining dormancy of isolated embryos and intact seeds of Euonymus alatus - Chandra Thammina; Mingyang He; Hao Yu; Yongqin Chen; Ying Gai; Kaishuang Cao; Litang Lu; Degang Zhao; Yuejin Wang; Richard McAvoy; Donna Ellis; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Production of cyclic adenosine monophosphate by Arthrobacter sp. A302 using fed-batch fermentation with pH-shift control - Jiaming Cao; Xiaochun Chen; Huajing Ren; Jindan Zhang; Lei Li; Yong Chen; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2012)

Identification and characterization of a new naringinase-producing strain, Williopsis californica Jmudeb007 - Hui Ni; Lijun Li; Anfeng Xiao; Ying Cao; Yuelong Chen; Huinong Cai (World Journal of Microbiology and Biotechnology, 2011)

Physical and Mechanical Properties of Fine-Grained Soil in the Zhejiang-Fujian Coastal Area, China - Yuan-Qin Xu; Pei-Ying Li; Ping Li; Le-Jun Liu; Cheng-Xiao Cao; Xiu-Li Feng (Marine Georesources & Geotechnology, 2011)

Dynamic mathematical models of batch experiments and fed-batch cultures for cyclic adenosine monophosphate production by Arthrobacter A302 - Lei Li; Xiaochun Chen; Huajing Ren; Jiaming Cao; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2011)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Weight-reducing effect of Acer truncatum Bunge may be related to the inhibition of fatty acid synthase - Wen-Hua Zhao; Li-Fang Gao; Wen Gao; Yong-Sheng Yuan; Chun-Chun Gao; Li-Ge Cao; Zi-Zheng Hu; Jian-Qiang Guo; Ying-Xia Zhang (Natural Product Research, 2011)

A polygalacturonase inhibitory protein gene (BcMF19) expressed during pollen development in Chinese cabbage-pak-choi - Li Huang; Ying Liu; Xiaolin Yu; Xun Xiang; Jiashu Cao (Molecular Biology Reports, 2011)

Isolation and identification of a phosphate-solubilizing bacterium Pantoea stewartii subsp. stewartii g6, and effects of temperature, salinity, and pH on its growth under indoor culture conditions - Xiao-Juan Hu; Zhuo-Jia Li; Yu-Cheng Cao; Jun Zhang; Ying-Xue Gong; Yu-Feng Yang (Aquaculture International, 2010)

Incidence and risk of significantly raised blood pressure in cancer patients treated with bevacizumab: an updated meta-analysis - Mao Mao An; Zui Zou; Hui Shen; Ping Liu; Meng Li Chen; Yong Bing Cao; Yuan Ying Jiang (European Journal of Clinical Pharmacology, 2010)

Upregulation of PTEN by peroxynitrite contributes to cytokine-induced apoptosis in pancreatic β-cells - Rongrong Hou; Jing Zhang; Tao Yin; Hongwei Cao; Nanyan Zhang; Xiaomiao Li; Li Wang; Ying Xing; Deqiang Li; Qiuhe Ji (Apoptosis, 2010)

Propranolol regulates cardiac transient outward potassium channel in rat myocardium via cAMP/PKA after short-term but not after long-term ischemia - Li Zhang; Chao-Qian Xu; Yuan Hong; Jia-Lin Zhang; Ying Liu; Mei Zhao; Yan-Xiu Cao; Yan-Jie Lu; Bao-Feng Yang; Hong-Li Shan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Effects of Reactive Oxygen Species Metabolic System on Soybean (Glycine max) Under Exogenous Chitosan to Ozone Stress - Tian Hong Zhao; Jun Li Wang; Yan Wang; Jia Wei Sun; Ying Cao (Bulletin of Environmental Contamination and Toxicology, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

Characteristics of the precipitation over the eastern edge of the Tibetan Plateau - Yueqing Li; Dejun Li; Song Yang; Cao Liu; Aihua Zhong; Ying Li (Meteorology and Atmospheric Physics, 2010)

Activation of p38 MAPK Pathway by Hepatitis C Virus E2 in Cells Transiently Expressing DC-SIGN - Qiu-Li Chen; Shi-Ying Zhu; Zhong-Qi Bian; Lan-Juan Zhao; Jie Cao; Wei Pan; Zhong-Tian Qi (Cell Biochemistry and Biophysics, 2010)

A novel carbonyl reductase from Pichia stipitis for the production of ethyl (S)-4-chloro-3-hydroxybutanoate - Qi Ye; Ming Yan; Lin Xu; Hou Cao; Zhenjiang Li; Yong Chen; Shuya Li; Hanjie Ying (Biotechnology Letters, 2009)

Hypertonic stimulation induces synthesis and release of glutamate in cultured rat hypothalamic astrocytes and C6 cells - Rong Cao; Shan Jiang; Li Duan; Ying-Fei Xiong; Bei Gao; Zhi-Ren Rao (Neuroscience Bulletin, 2008)

Using oligonucleotide suspension arrays for laboratory identification of bacteria responsible for bacteremia - Xiao-li Hou; Han-liang Jiang; Qing-yi Cao; Li-ying Zhao; Barbara J. Chang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2008)

Effect of lead on ERK activity and the protective function of bFGF in rat primary culture astroglia - Ying Zhang; Li-ping Ye; Biao Wang; Shi-cheng Cao; Li-guang Sun (Journal of Zhejiang University-SCIENCE B, 2007)

Functional analysis of the α-neurotoxin, BmαTX14, derived from the Chinese scorpion, Buthus martensii Karsch - Kun Wang; Shi-Jin Yin; Meng Lu; Hong Yi; Chao Dai; Xiu-Jing Xu; Zhi-Jian Cao; Ying-Liang Wu; Wen-Xin Li (Biotechnology Letters, 2006)

Inhibition of Japanese Encephalitis Virus NS1 Protein Expression in Cell by Small Interfering RNAs - Xueqin Liu; Shengbo Cao; Rui Zhou; Gaoyuan Xu; Shaobo Xiao; Ying Yang; Minxuan Sun; Yaoming Li; Huanchun Chen (Virus Genes, 2006)

Localization of putative stem cells and four cell populations with different differentiation degree in mouse mammary anlagen - Jianyong Han; Suying Cao; Hong Jin; Ying Liu; Meili Wang; Jiazhe Song; Ning Li (Histochemistry and Cell Biology, 2006)

A novel dual peroxisome proliferator-activated receptors α and γ agonist with beneficial effects on insulin resistance and lipid metabolism - Cheng Xu; Li-Li Wang; Hong-Ying Liu; Cheng-Mai Ruan; Xing-Bo Zhou; Ying-Lin Cao; Song Li (Biotechnology Letters, 2006)

The influence of feeding rate on growth, feed efficiency and body composition of juvenile grass carp (Ctenopharyngodon idella) - Zhen-Yu Du; Yong-Jian Liu; Li-Xia Tian; Jian-Guo He; Jun-Ming Cao; Gui-Ying Liang (Aquaculture International, 2006)

Cloning and expression study of a putative high-affinity nitrate transporter gene from Dunaliella salina - Qinghua He; Dairong Qiao; Qinglian Zhang; Yin Li; Hui Xu; Liang Wei; Ying Gu; Yi Cao (Journal of Applied Phycology, 2004)